Radiopaque Glass Materials
Radiopaque glass materials with enhanced densities and radiopacity address the challenge of visualizing particulate embolic agents during angioembolization, improving treatment precision by ensuring clear imaging and distribution within the vasculature.
Patent Information
- Application Number
- JP2021563261
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-31
- Filing Date
- 2020-06-01
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-06-01
AI Technical Summary
Particulate embolic agents used in angioembolization are often not radiopaque, making them difficult to visualize during or after treatment with conventional radiographic imaging unless treated with a contrast agent.
Development of radiopaque glass materials with densities ranging from approximately 2.7 to 4.3 g/cm³, incorporating components like Y₂O₃, BaO, and Ta₂O₅ to enhance radiopacity, allowing for improved visibility during vascular embolization procedures.
The glass materials exhibit radiopacity greater than 9,000 HU at 120 kVp, enabling effective visualization and distribution within the vasculature, facilitating more precise therapeutic interventions.
Smart Images

Figure 0007610526000012 
Figure 0007610526000013 
Figure 0007610526000014
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 62 / 855,285, filed May 31, 2019, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to radiopaque glass materials suitable for forming microparticles that can be administered to a patient. [Background technology]
[0003] The following paragraphs are not an admission that anything discussed therein is prior art or part of the knowledge of those skilled in the art.
[0004] Therapeutic vascular occlusion (embolization) is a technique used to treat certain pathological conditions in situ. Therapeutic embolization is generally performed using catheters to place embolic agents in the circulatory system, such as blood vessels of various processes (tumors, vascular malformations, and bleeding processes). Summary of the Invention [Problem to be solved by the invention]
[0005] The following preamble is intended to introduce the specification to the reader, but does not define the invention. One or more inventions may reside in a combination or subcombination of the apparatus elements or method steps described below or elsewhere in this document. The inventors do not waive or withdraw their claims to any invention disclosed herein merely by the absence of recitation of another invention or inventions in the claims.
[0006] Particulate embolic agents used in vascular embolization may not be radiopaque and therefore are difficult to see with radiological imaging unless the particulate embolic agent is treated with a contrast agent before being injected. TheraSphere™ Yttrium-90 microparticles are commercially available radioactive microparticles that have been used to treat primary and metastatic liver cancer and have a radiopacity of approximately 6,000 Hounsfield Units (HU) at 120 kVp.
[0007] Radiopaque particulate embolic agents are desirable because they can be viewed by radiographic imaging during or after embolization therapy. One or more of the examples described in this disclosure attempt to provide a radiopaque glass material that has greater radiopacity than particulate embolic agents by other means. [Means for solving the problem]
[0008] The glass material ultimately intended for use in vascular embolization has a viscosity of about 2.7 g / cm 3 ~Approx. 4.3g / cm 3 In a particular example, the glass material may have a density of about 2.9 g / cm 3 ~Approx. 3.7g / cm 3 , or about 3.3 g / cm 3 ~Approx. 3.6g / cm 3 Particles having a density in this range are believed to distribute adequately within the vasculature of a patient.
[0009] In the glass materials of the present disclosure, Y2O3, BaO, and Ta2O5 all contribute to the radiopacity of the glass. However, increasing the amount of these components also increases the density of the resulting glass material. The authors of the present disclosure have identified glass compositions that provide desirable values of radiopacity at densities suitable for vascular embolization. Some glass materials of the present disclosure may have a radiopacity of greater than 9,000 HU at 120 kVp. Some glass materials of the present disclosure have a radiopacity of about 2.7 g / cm 3 ~Approx. 4.3g / cm 3 , for example, about 2.9 g / cm 3 ~Approx. 3.7g / cm3 , or about 3.3 g / cm 3 ~Approx. 3.6g / cm 3 The density of the sintered body may be 0.01 to 0.01.
[0010] In one aspect, the present disclosure provides a glass material comprising about 0.55 to about 0.85 mole fraction of SiO2, about 0.01 to about 0.23 mole fraction of Na2O, K2O, or a combination of Na2O and K2O, about 0.05 to about 0.28 mole fraction of Y2O3, BaO, or a combination of Y2O3 and BaO, and optionally Ta2O5, wherein the sum of Y2O3, BaO, and optionally Ta2O5 is about 0.10 to about 0.31 mole fraction.
[0011] In some examples, the glass material includes about 0.03 to about 0.23, such as about 0.05 to about 0.23, mole fraction of Na2O, K2O, or a combination of Na2O and K2O.
[0012] In some examples, the glass material includes a mole fraction of SiO2 of about 0.55 to about 0.82, such as about 0.55 to about 0.80.
[0013] In a particular example, the glass material includes about 0.55 to about 0.80 mole fraction of SiO2, and about 0.05 to about 0.22 mole fraction of Na2O, K2O, or a combination of Na2O and K2O.
[0014] In one particular example, the glass material includes about 0.74 mole fraction SiO2, about 0.09 mole fraction Na2O, about 0.085 mole fraction BaO, about 0.085 mole fraction Ta2O5, and about 0.006 mole fraction B2O3. This particular glass material exhibits a radiopacity of about 16,000 HU at 120 kVp.
[0015] In another particular example, the glass material includes about 0.79 mole fraction of SiO2; about 0.06 mole fraction of Na2O; about 0.08 mole fraction of BaO; about 0.07 mole fraction of Ta2O5; and about 0.003 mole fraction of B2O3.
[0016] In yet another particular example, the glass material includes about 0.77 mole fraction of SiO2; about 0.031 mole fraction of Na2O; about 0.10 mole fraction of BaO; about 0.096 mole fraction of Ta2O5; and about 0.002 mole fraction of B2O3.
[0017] In yet another particular example, the glass material includes about 0.80 mole fraction SiO2; about 0.033 mole fraction Na2O; about 0.82 mole fraction BaO; about 0.085 mole fraction Ta2O5; and about 0.001 mole fraction B2O3.
[0018] In some examples of the present disclosure, the glass material of the present disclosure is bulk glass. The term "bulk glass" refers to a glass material obtained by forming glass from starting materials that have not undergone any additional processing to produce a glass material suitable for vascular embolization. For example, a glass material produced on a commercial scale without any processing steps to produce an irregular particulate glass material may be considered a bulk glass.
[0019] In another example, the glass material of the present disclosure is an irregular particulate glass material. The term "irregular particulate glass material" refers to a particulate material that is sized for vascular embolization but is not properly shaped. Irregular particulate glass material can be prepared by crushing bulk glass, sieving the resulting particles, and recovering particulates of the desired size.
[0020] In yet another example, the glass material of the present disclosure is a substantially spherical particulate glass material. The term "substantially spherical particulate glass material" refers to a particulate material that is sized and shaped for vascular embolization. The substantially spherical particulate glass material may be prepared by remelting the surface of an irregular particulate glass material and forming substantially spherical grains.
[0021] In another aspect, a method of making the glass material of the present disclosure is provided.
[0022] In yet another aspect of the present disclosure, the substantially spherical particulate glass material as described herein may be used in X-ray based radiological imaging techniques, such as radiological imaging, computed tomography (CT) imaging, cone beam CT imaging, or fluoroscopic imaging. The present disclosure further provides a method of imaging a mammal with the substantially spherical particulate glass material described herein.
[0023] In vascular embolization therapy using radioactive microparticles, it is believed that administering more microparticles with lower specific activity is desirable because increasing the number of microparticles provides better tumor coverage than administering fewer microparticles with higher specific activity. Without wishing to be bound by theory, the authors of this disclosure believe that microparticles will remain in the first effective localization spot in the blood vessel they encounter. Administration of a small amount of microparticles may cause some particles to concentrate in one part of the tumor if there are enough localization spots to interact with the majority of the administered particles. In contrast, administering more particles with low specific activity will result in a higher saturation of the effective localization spot and a more uniform tumor coverage.
[0024] For at least some tumor sizes and / or degrees of vascularization, administering to a patient a mixture of (i) radioactive microparticles and (ii) radiopaque, non-radioactive microparticles according to the present disclosure may provide at least some of the benefits associated with administering more microparticles with lower specific activity, even if the individual radioactive microparticles have a higher specific activity.
[0025] In one aspect, the present disclosure provides a mixture of (i) radioactive glass particulates and (ii) a non-radioactive radiopaque particulate glass material according to the present disclosure, the radioactive glass particulates being suitable for treating tumors in the liver, and the radioactive glass particulates and the non-radioactive radiopaque particulate glass material are substantially the same size. In a particular example, the particulate glass material of the present disclosure and the radioactive glass particulates are substantially the same density.
[0026] In some examples, the mixture may be prepared by exposing pre-radioactive glass particulate to neutron radiation to form radioactive glass particulate, and mixing the radioactive glass particulate with a radiopaque particulate glass material of the present disclosure.
[0027] In a particular example, the mixture includes (i) substantially spherical radioactive yttrium oxide aluminosilicate glass particulates comprising about 40% by weight SiO, about 20% by weight AlO, and about 40% by weight YO (corresponding to about 0.170 mole fraction YO, about 0.189 mole fraction AlO, and about 0.641 mole fraction SiO), and (ii) a substantially spherical particulate glass material comprising about 0.73 to about 0.80 mole fraction SiO, about 0.03 to about 0.11 mole fraction NaO, about 0.07 to about 0.10 mole fraction BaO, about 0.07 to about 0.10 mole fraction TaO, and about 0.001 to about 0.006 mole fraction BO.
[0028] In yet another aspect of the present disclosure, when the mixture includes radioactive glass microspheres, radiation is delivered to the mammal by administering the mixture to the mammal. Such methods may additionally include imaging the mammal using X-ray based radioimaging techniques, particularly using static imaging techniques. Imaging techniques may include fluoroscopy, computed tomography / positron emission tomography (CT / PET), or cone beam computed tomography (CBCT).
[0029] Glass materials according to the present disclosure may be included in compositions or delivery devices or may be used in diagnostic or therapeutic methods.
[0030] In some aspects, the present disclosure provides therapeutic or diagnostic compositions comprising a mixture of radioactive and non-radioactive particles, at least some of the non-radioactive particles comprising a glass material of the present disclosure.
[0031] In another aspect, the disclosure provides a method comprising administering a therapeutic or diagnostic composition to a patient, the administration being by intravascular, intraperitoneal, or transdermal delivery.
[0032] In one aspect, the present disclosure provides a delivery device for intravascular, intraperitoneal, or transdermal delivery of a mixture of radioactive and non-radioactive microparticles to a patient. The delivery device is fluidly coupleable to a mixed transport medium. The delivery device includes a fluid inlet fluidly coupleable to the mixed transport medium, a fluid outlet, a fluid mixer fluidly coupled to the fluid inlet and the fluid outlet, a radioactive microparticle source fluidly coupled to the fluid mixer, and a non-radioactive microparticle source fluidly coupled to the fluid mixer. At least some of the non-radioactive microparticles are comprised of a glass material according to the present disclosure. The radioactive microparticle source is distinct from the non-radioactive microparticle source. The fluid mixer mixes the radioactive microparticles with the non-radioactive microparticles and delivers the mixture of radioactive and non-radioactive microparticles out of the fluid outlet utilizing the mixed transport medium.
[0033] In another aspect, the present disclosure provides a delivery device for intravascular, intraperitoneal, or transdermal delivery of a mixture of radioactive and non-radioactive microparticles to a patient. The delivery device includes at least one fluid inlet fluidly connectable to a transport medium, a radioactive microparticle source fluidly connected to the at least one fluid inlet, a radioactive microparticle source fluidly connected to the at least one fluid inlet, a first fluid outlet fluidly connected to the radioactive microparticle source, and a second fluid outlet fluidly connected to the non-radioactive microparticle source. At least some of the non-radioactive microparticles are comprised of a glass material according to the present disclosure. The radioactive microparticle source is distinct from the non-radioactive microparticle source.
[0034] In the context of the present disclosure, one collection of microparticles should be understood to be distinct from another collection of microparticles when the two collections are not mixed. For example, radioactive microparticles in the barrel of one syringe should be understood to be distinct from non-radioactive microparticles in the barrel of a second syringe, even if the two syringes are fluidly coupled and capable of expelling microparticles to form a mixture.
[0035] In yet another aspect, the present disclosure provides a method comprising mixing (i) a first population of radioactive particles and (ii) a second population of non-radioactive particles, and administering to a patient a therapeutically or diagnostically appropriate amount of the mixture, at least some of the non-radioactive particles being comprised of a glass material according to the present disclosure.
[0036] In yet another aspect, the present disclosure provides a method of administering a suitable amount of microparticles to a patient for therapeutic or diagnostic use, the method comprising administering non-radioactive microparticles to the patient and administering radioactive microparticles to the patient without first detecting the non-radioactive microparticles, at least some of the non-radioactive microparticles being comprised of a glass material according to the present disclosure, the administration being by intravascular, intraperitoneal, or transdermal delivery, the route of administration of the non-radioactive microparticles being the same as the route of administration of the radioactive microparticles.
[0037] In yet another aspect, the present disclosure provides a method of administering a therapeutically or diagnostically appropriate amount of microparticles to a patient, the method comprising administering radioactive microparticles to the patient and administering non-radioactive microparticles to the patient without first detecting the radioactive microparticles, at least some of the non-radioactive microparticles being comprised of a glass material according to the present disclosure, the administration being by intravascular, intraperitoneal, or transdermal delivery, the route of administration of the non-radioactive microparticles being the same as the route of administration of the radioactive microparticles.
[0038] In yet another aspect, the present disclosure provides a method of administering a suitable amount of microparticles for therapeutic or diagnostic use, the method comprising co-administering to a patient (i) a first population of radioactive microparticles and (ii) a second population of non-radioactive microparticles, at least some of which are comprised of a glass material according to the present disclosure.
[0039] In yet another aspect, the present disclosure provides a method of administering a suitable amount of microparticles for therapeutic or diagnostic purposes, the method comprising sequential administration of non-radioactive and radioactive microparticles to a patient in a single treatment session, at least some of the non-radioactive microparticles being comprised of a glass material according to the present disclosure.
[0040] In yet another aspect, the present disclosure provides a method comprising sequentially administering to a patient (i) therapeutic radioactive microparticles and then (ii) non-radioactive microparticles, at least some of which are comprised of a glass material according to the present disclosure.
[0041] In any of the above embodiments, the non-radioactive particulates may be any of the non-radioactive glass compositions discussed below in the section entitled "Glass Compositions" and / or may have any of the features, alone or in combination, of the glass materials discussed below in the section entitled "Glass Materials." In any of the above embodiments, the radioactive particulates may be any of the radioactive glass compositions described in the sections below for radiotherapeutic mixtures. [Brief description of the drawings]
[0042] Embodiments of the present disclosure will now be described, by way of example only, with reference to the accompanying drawings, in which:
[0043] [Figure 1] FIG. 1 is a graph showing cumulative ion release curves obtained for an exemplary glass composition of the present disclosure (spheres, post-spheronization) extracted in calcium- and magnesium-free phosphate buffered saline (CMF-PBS).
[0044] [Figure 2A] FIG. 2A is a set of SEM images at 250x and 1000x of irregular BIC2 glass powder.
[0045] [Figure 2B] FIG. 2B is a set of SEM images at 250x and 1000x of BIC2 microparticles after spheronization.
[0046] [Figure 2C] FIG. 2C is a set of SEM images at 250x and 1000x of BIC2 microparticles after spheronization and sieved after treatment (24 hours).
[0047] [Figure 2D] FIG. 2D is a set of SEM images at 250x and 1000x of BIC2 microparticles after spheronization and sieved after treatment (72 hours).
[0048] [Diagram 3] FIG. 3 is a graph showing CT radiopacity as a function of volume fraction of various glass particulates.
[0049] [Figure 4] FIG. 4 is a graph showing R1 relaxivity as a function of volume fraction of various glass microspheres.
[0050] [Diagram 5] FIG. 5 shows representative images of T1-weighted, T2-weighted and T2*-weighted BIC2 and COMP1 at various fractional volumes.
[0051] [Figure 6] FIG. 6 is a graph showing R2 relaxivity as a function of volume fraction of various glass microspheres.
[0052] [Figure 7] FIG. 7 is a graph showing R2* relaxivity as a function of volume fraction of various glass microspheres.
[0053] [Figure 8] FIG. 8 is a graph showing local magnetic dose (LMD) relaxivity obtained from MRI susceptometry measurements as a function of the volume fraction of various glass microspheres. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] In the context of this disclosure, a "glass material" should be understood generally as a physical material, such as a bulk or particulate material, and should be understood to include glasses of a specified composition. The term "glass" or "glass composition" defines the specific components of the composition. Thus, references to physical properties of the material (e.g., particle size) relate to the glass material, while references to compositional properties (e.g., mole fraction) relate to the glass or glass composition. In some parts of this disclosure, the terms "glass," "glass composition," and "glass material" are used interchangeably as if they all refer to the same component, such as when a glass material is composed solely of a described glass composition.
[0055] In the context of this disclosure, disclosed ranges of values should be interpreted in an open manner to include not only the numerical values explicitly recited as the limits of the range, but also all of the individual numerical values or subranges subsumed within the range, as if each numerical value and subrange were explicitly recited. For example, the range "about 1 to about 10" should be interpreted not only to include about 1 to about 10, but also to include the individual values (e.g., 1, 1.5, 2, 4, etc.) and subranges (e.g., 1 to 3, 2 to 7, 5 to 6, etc.) within the disclosed range of values.
[0056] Glass composition Generally, the present disclosure provides a glass material, the glass comprising about 0.55 to about 0.85 mole fraction of SiO2, and about 0.01 to about 0.23 mole fraction of Na2O, K2O, or a combination of Na2O and K2O. The amount of Y2O3, BaO, and Ta2O5 in the glass all affect the radiopacity and density of the glass, and may additionally affect the performance of other components to form the glass, so the allowable amount of Y2O3, BaO, and / or Ta2O5 is traditionally unpredictable. Based on experimental results, the authors of the present disclosure have determined that the glass material of the present disclosure comprises about 0.05 to about 0.28 mole fraction of Y2O3, BaO, or a combination of Y2O3 and BaO, and optional Ta2O5, and the sum of Y2O3, BaO, and optional Ta2O5 should be about 0.10 to about 0.31 mole fraction. In some examples, the sum of Y2O3, BaO, and optionally Ta2O5 may be from about 0.10 to about 0.25 mole fraction, such as from about 0.10 to about 0.15 mole fraction.
[0057] In the context of mole fractions, "about X mole fraction" should be understood to mean any value within the range of estimated uncertainties associated with the stated value and the oxide being measured. For example, in the context of inductively coupled plasma mass spectrometry (ICP-MS), the estimated uncertainty for SiO2 may be 1% of the reported value, the estimated uncertainty for Na2O may be 10% of the reported value, the estimated uncertainty for BaO may be 2% of the reported value, and the estimated uncertainty for Ta2O5 may be 1% of the reported value.
[0058] The glasses of the present disclosure may contain about 0.05 to about 0.08 mole fractions of Y2O3, BaO, or a combination of Y2O3 and BaO. Some exemplary glasses of the present disclosure do not contain any Y2O3. Such exemplary glasses may be useful in particulate mixtures, as discussed in more detail below.
[0059] The glasses of the present disclosure may include Ta2O5 in an amount up to about 0.12 mole fraction, such as up to about 0.10 mole fraction Ta2O5, such as from about 0.05 to about 0.12 mole fraction, such as from about 0.05 to about 0.10 mole fraction Ta2O5.
[0060] The glasses of the present disclosure may additionally include B2O3 in an amount up to 0.20 mole fraction. The sum of B2O3 and SiO2 may be about 0.60 to about 0.85, e.g., about 0.60 to about 0.80 mole fraction. B2O3 is known in the art as a glass former, and the inclusion of B2O3 in sodium silicate glasses results in sodium borosilicate glasses. Some examples of the sodium borosilicate glasses of the present disclosure may be more resistant to degradation. Some examples of the sodium borosilicate glasses of the present disclosure may have improved glass forming ability.
[0061] While this disclosure focuses on sodium silicate glasses, both Na2O and K2O are known to act as modifiers of the glass network and have many similar effects on glass properties. In some contemplated glasses of this disclosure, the glass composition may include only Na2O (no K2O), or only K2O (no Na2O). In other contemplated glasses, the glass composition may include Na2O and K2O in a ratio of 100:1 to 1:100. This disclosure further contemplates ratios such as 50:1, 25:1, 10:1, 5:1, 1:1, 1:5, and 1:10, and any range of ratios therebetween. In some examples of this disclosure, the Na:K ratio may be about 75:25, about 50:50, about 25:75, or about 10:90.
[0062] In addition to its effect on the radiopacity of the glass, BaO is known in the art to act as a modifier of the glass network. If the total amount of network modifier in the sodium silicate glass is too high, the glass may not form or may be unsuitable as a durable embolization agent due to the instability of the glass network. In the glass material of the present disclosure containing BaO, the sum of BaO, Na2O, and K2O may be about 0.10 to about 0.33 mole fraction, for example, about 0.15 to about 0.33 mole fraction. For example, the sum of BaO, Na2O, and K2O may be about 0.10 to about 0.25, for example, about 0.15 to about 0.25 mole fraction.
[0063] The glasses of the present disclosure are preferably predominantly sodium silicate glasses. The sum of SiO2 and Na2O in the glasses of the present disclosure may be from about 0.65 to about 0.90 mole fraction.
[0064] In some examples of glass materials disclosed herein, the sum of SiO2 and Na2O is about 0.69 to about 0.90 mole fraction, the glass includes Ta2O5 in a mole fraction of about 0.05 to about 0.09, and the sum of Y2O3, BaO, and Ta2O5 is about 0.10 to about 0.17 mole fraction. Exemplary glass materials of such compositions have high levels of radiopacity and a viscosity of 3.3 to 3.6 g / cm 3 This represents a beneficial balance between the amount of heat and the particle density.
[0065] In another example of the glass material disclosed herein, the sum of SiO2 and Na2O is about 0.65 to about 0.80 mole fraction, the glass includes Ta2O5 at about 0.05 to about 0.10 mole fraction, and the sum of Y2O3, BaO, and Ta2O5 is about 0.18 to about 0.31 mole fraction. Exemplary glass materials of such compositions may exhibit high levels of radiopacity while being dense.
[0066] In yet another example of the glass materials disclosed herein, the glass comprises about 0.55 to about 0.80, e.g., about 0.55 to about 0.75, mole fraction of SiO2; about 0.03 to about 0.23, e.g., about 0.05 to about 0.22, mole fraction of Na2O; about 0.05 to about 0.12, e.g., about 0.05 to about 0.08, mole fraction of YO3, BaO, or a combination of YO3 and BaO; and about 0.05 to about 0.12, e.g., about 0.05 to about 0.09, mole fraction of Ta2O5.
[0067] For example, the glass may include about 0.70 to about 0.73 mole fraction of SiO2, about 0.16 to about 0.18 mole fraction of Na2O, about 0.05 to about 0.7 mole fraction of Y2O3, and about 0.05 to about 0.7 mole fraction of Ta2O5. One particular example is a glass that includes about 0.71 mole fraction of SiO2, about 0.17 mole fraction of Na2O, about 0.06 mole fraction of Y2O3, and about 0.06 mole fraction of Ta2O5. Another particular example is a glass that includes about 0.72 mole fraction of SiO2, about 0.17 mole fraction of Na2O, about 0.05 mole fraction of Y2O3, and about 0.06 mole fraction of Ta2O5.
[0068] In some examples of the glass materials disclosed herein, the glass comprises about 0.55 to about 0.82, e.g., about 0.55 to about 0.75, mole fraction of SiO; about 0.03 to about 0.23, e.g., about 0.05 to about 0.22, mole fraction of NaO; about 0.05 to about 0.12, e.g., about 0.05 to about 0.08, mole fraction of Y2O3, BaO, or a combination of Y2O3 and BaO; about 0.05 to about 0.12, e.g., about 0.05 to about 0.09, mole fraction of Ta2O5; and up to 0.1 mole fraction of B2O3.
[0069] In some examples, the glass comprises about 0.65 to about 0.82, e.g., about 0.73 to about 0.80, mole fraction of SiO2, about 0.03 to about 0.23, e.g., about 0.03 to about 0.11, mole fraction of Na2O, about 0.06 to about 0.12, e.g., about 0.07 to about 0.10, mole fraction of BaO, about 0.06 to about 0.12, e.g., about 0.07 to about 0.10, mole fraction of Ta2O5, and about 0.001 to about 0.015, e.g., about 0.001 to about 0.006, mole fraction of B2O3.
[0070] One particular example is a glass that includes about 0.69 mole fraction SiO2, about 0.16 mole fraction Na2O, about 0.07 mole fraction BaO, about 0.07 mole fraction Ta2O5, and about 0.01 mole fraction B2O3.
[0071] Another specific example is a glass that includes about 0.66 mole fraction SiO2, about 0.20 mole fraction Na2O, about 0.065 mole fraction BaO, about 0.06 mole fraction Ta2O5, and about 0.011 mole fraction B2O3.
[0072] Another specific example is a glass that includes about 0.73 mole fraction SiO2, about 0.10 mole fraction Na2O, about 0.08 mole fraction BaO, about 0.08 mole fraction Ta2O5, and about 0.01 mole fraction B2O3.
[0073] Yet another specific example is a glass that includes about 0.74 mole fraction SiO2, about 0.09 mole fraction Na2O, about 0.085 mole fraction BaO, about 0.085 mole fraction Ta2O5, and about 0.006 mole fraction B2O3.
[0074] Yet another specific example is a glass that includes about 0.79 mole fraction SiO2, about 0.06 mole fraction Na2O, about 0.08 mole fraction BaO, about 0.07 mole fraction Ta2O5, and about 0.003 mole fraction B2O3.
[0075] A further specific example is a glass that includes about 0.77 mole fraction SiO2, about 0.031 mole fraction Na2O, about 0.10 mole fraction BaO, about 0.096 mole fraction Ta2O5, and about 0.002 mole fraction B2O3.
[0076] Yet another specific example is a glass that includes about 0.80 mole fraction SiO2, about 0.033 mole fraction Na2O, about 0.082 mole fraction BaO, about 0.085 mole fraction Ta2O5, and about 0.001 mole fraction B2O3.
[0077] A further example is a glass that includes about 0.58 mole fraction SiO2, about 0.20 mole fraction Na2O, about 0.06 mole fraction of a blend of Y2O3 and BaO, about 0.07 mole fraction Ta2O5, and about 0.09 mole fraction B2O3. The glass may also include about 0.024 mole fraction Y2O3 and about 0.035 mole fraction BaO.
[0078] The glass composition of the present disclosure is preferably substantially free of one or more of Li2O, Rb2O, V2O5, ZnO, FeO2, and fluoride. Lithium oxide, rubidium oxide, and vanadium oxide can be cytotoxic glasses if present in high enough concentrations and if these oxides leach from the glass material. These oxides are desirably present at 0.01, e.g., 0.001 or 0.0001 mole fraction, and preferably 0 mole fraction. Fluoride in the glass degrades physiological conditions. Desirably, fluoride is present at 0.005 mole fraction or less, e.g., 0.0001 mole fraction, and preferably 0 mole fraction. Zinc oxide can impair liver function if present in high enough concentrations and can be leached from the glass material. Desirably, zinc oxide is present at 0.01 mole fraction or less, e.g., 0.001 or 0.0001 mole fraction, and preferably 0 mole fraction. Desirably, the iron oxide is present in an amount of 0.01 mole fraction or less, for example, 0.001 or 0.0001 mole fraction, and preferably 0 mole fraction.
[0079] The authors of this disclosure have identified glass compositions that have particularly desirable properties for vascular embolization applications, which are shown in Table 1.
[0080] The compositions of the formulas "TRCR#" and "BIC#" are reported based on the relative amounts of starting materials, however, the compositions of the actual glasses produced may vary slightly from the theoretical compositions.
[0081] The compositions of the formulations "BIC#-IGP" are reported based on measurements of corresponding irregular glass powders that were sieved to collect particles smaller than 45 μm. These compositions are believed to more accurately reflect the actual composition of the glasses produced.
[0082] The compositions of the formulations "BIC#-MPS" are reported based on measurements of substantially spherical particulate glass material produced from the corresponding BIC#-IGP compositions. The glass microspheres were sieved to yield microspheres with an average size range of 20 μm to 30 μm. The composition of the irregular glass particles changes when the particles are flame treated to remelt the surfaces of the irregular particles and subsequently form substantially spherical grains.
[0083] The composition of the formulation "BIC#-MPC" is reported based on measurements of post-treated material produced from the corresponding BIC#. Substantially spherical particulate glass material was post-treated with 0.2 g / mL calcium and magnesium free phosphate buffered saline (CMF-PBS) at 50°C for 72 to 366 hours. The composition of the flame treated particles is altered when the particles are treated to reduce surface reaction deposits resulting from the flame treatment.
[0084] The composition of formulation "BIC2-MPC#" is reported based on measurements of particulate glass material produced from irregular BIC2 glass powder and processed to a substantially spherical shape, where the compositional differences in the formulations are the result of different flame treatment parameters. The irregular BIC2 glass powder was sieved to collect particles smaller than 45 μm, flame treated to remelt the surfaces of the irregular particles and form substantially spherical grains, sieved to obtain microspheres with an average size range of 20 μm to 30 μm, and post-treated at 80° C. for 72 hours in 0.2 g / mL calcium and magnesium free phosphate buffered saline (CMF-PBS).
[0085] The composition of the glass may vary when comparing (a) a portion of the starting reagents, (b) the measured composition of the produced glass, and (c) the substantially spherically processed microparticles useful for embolization angioplasty, but all of these should be understood in this disclosure to refer to the same angioembolization product at various stages of production. Thus, for example, a BIC2 composition based on theoretical mole percent of "about 0.69 mole fraction of SiO2" refers to (i) an irregular glass powder having "about 0.66 mole fraction of SiO2", (ii) a processed glass material having "about 0.73 mole fraction of SiO2", and (iii) a processed glass material having "about 0.74 mole fraction of SiO2", "about 0.77 mole fraction of SiO2", "about 0.79 mole fraction of SiO2", or "about 0.80 mole fraction of SiO2". Unless otherwise indicated, mole percent / fractions discussed herein refer to theoretical percent / fractions based on the amount of starting reagents. [Table 1]
[0086] The density of the irregular particulate glass material sieved to collect particles of 45 μm or less, the density of the substantially spherical particulate glass material, and the radiopacity of the substantially spherical glass composition are shown in Table 2. [Table 2]
[0087] In various tests, as disclosed in more detail below, the glass used in TheraSpher™ Yttrium-90 microspheres was used as a control, which contained 40% Y2O3, 20% Al2O3, and 40% SiO2 by weight (referred to herein as "YAS4" or "COMP1"). The YAS4 irregular glass powder was sieved to collect particles 45 μm or smaller and had a measured composition of 65.795 mol% SiO2 (36.56% by weight), 19.111 mol% Al2O3 (20.90% by weight), and 15.095 mol% Y2O3 (42.40% by weight). The substantially spherical particulate YAS4 glass had a measured composition of 64.448 mol % SiO2 (38.12 wt %), 19.492 mol % Al2O3 (20.89 wt %), and 16.060 mol % Y2O3 (40.70 wt %).
[0088] In contrast to the exemplary glass compositions above, YAS4 glass is an irregular glass powder that has been sieved to collect particles 45 μm or smaller and has a mass of 3.3466±0.0060 g / cm 3 3.3078±0.0077g / cm for a substantially spherical material 3 and when measured using a CT radiopacity measurement method, the substantially spherical material has a CT radiopacity of 10,387±245 HU at 70 kVp and a CT radiopacity of 5,955±202 HU at 120 kVp for the substantially spherical material.
[0089] Glass formulations TRCR3, TRCR9, TRCR12, TRCR13, TRCR16, TRCR23, BIC1-MPS, BIC2-MPS, and BIC3-MPS all exhibit CT radiopacity of greater than 13,000 HU at 120 kVp, which is more than twice the radiopacity of the control YAS4 glass composition. Of these formulations, TRCR3, TRCR9, TRCR13, BIC1-MPS, BIC2-MPS, and BIC3-MPS are substantially spherical particulate glass materials with densities within 10% of the density of the control YAS4 glass composition.
[0090] Glass Material The substantially spherical microparticles according to the present disclosure may be useful for embolic angioplasty and are manufactured by first forming bulk glass. The bulk glass is then processed to provide an irregular particulate glass material according to the present disclosure. The irregular microparticles are flame treated to form substantially spherical microparticles. Flame treatment of irregular glass microparticles to form substantially spherical microparticles is well known in the art. Examples of flame treatment include flame sphering, ultrasonic spray pyrolysis, droplet generators, and vertical thermal flames. Various glass compositions of the present disclosure may be melted at various temperatures. The flame treatment process used to remelt the surface of the irregular microparticles may use various gases or gas mixtures, such as propane-oxygen or acetylene-oxygen, to provide a temperature capable of remelting the surface of the irregular glass microparticles of interest. The microparticles that are flame-sphered may be treated to reduce or remove surface reaction deposits resulting from the flame treatment.
[0091] In the context of the present disclosure, the terms "microparticles" and "microparticles" can be used interchangeably and refer to particles having a diameter of less than 1200 μm. In a mixture of particles, the mixture has an average diameter of 1200 μm.
[0092] Although the present disclosure may refer to "microspheres" or "glass microspheres" or "spherical particles," it should be understood that the particles of the present disclosure need not be perfectly spherical. In the context of the present disclosure, "substantially spherical" refers to a mixture of particles having a mean sphericity (%SPHT) of at least 90%. Sphericity (%SPHT) can be measured using a CamSizer P4 (ATS Scientific, Burlington, ON) system, which operates based on dynamic image analysis principles, according to ISO 9276-6 and ISO 133322-2, respectively.
[0093] The %SPHT can be determined using the following formula:
number
[0094] The terms "microspheres" and "substantially spherical microparticles" may be used interchangeably and refer to substantially spherical particles having an average diameter of less than 1200 μm. A mixture of microparticles has an average diameter of less than 1200 μm.
[0095] Bulk glasses according to the present disclosure can have glass compositions as described above, which can reflect the theoretically indicated mol% of the components. One specific example of such a bulk glass is BIC2 glass, which has a theoretical composition of 0.687 mole fraction SiO2, 0.163 mole fraction Na2O, 0.068 mole fraction BaO, about 0.070 mole fraction Ta2O5, and about 0.012 mole fraction B2O3.
[0096] Irregular particulates can be produced by grinding bulk glass using any technique known in the art, such as a planetary ball mill with ZrO2 grinding media, and sieving the resulting particles to recover particles of the desired size. The use of ZrO2 as the grinding media can help reduce contaminants in the process due to the toughness of the grinding media relative to the bulk glass. One specific example of irregular particulates according to the present disclosure is BIC2-IGP glass, which has 0.659 mole fraction of SiO2, 0.146 mole fraction of Na2O, 0.065 mole fraction of BaO, about 0.062 mole fraction of Ta2O5, and about 0.011 mole fraction of B2O3. Other specific examples are BIC1-IGP and BIC3-IGP glasses.
[0097] The irregular microparticles may have an average diameter of about 15 μm to about 1200 μm. Microparticles of various sizes may be used for various vascular embolization protocols. Microparticles of the present disclosure may be selected to distribute preferentially in tumor vasculature over normal tissue. The size of the microparticles affects this distribution. Microparticles according to the present disclosure, useful for example for making microspheres for visualizing or treating liver tumors, may have an average diameter of about 15 μm to about 45 μm. In certain examples, the microparticles may have an average diameter of about 20 μm to about 35 μm. In other examples, the irregular microparticles of the present disclosure may be sieved to provide particles of about 40 μm to about 500 μm, about 40 μm to about 300 μm, about 300 μm to about 500 μm, about 500 μm to about 700 μm, or about 700 μm to about 1200 μm. The microspheres obtained from the various sizes of microparticles may be selected depending on the inner diameter of the blood vessel to be occluded. For example, blood vessels that supply blood to support tumor growth, but are distant from solid tumours, may be larger in diameter than blood vessels found within the tumor, and it may be desirable to use larger particles to block larger blood vessels, even if microspheres are not useful for visualizing the tumor itself.
[0098] It should be understood that "about X μm" in the context of particle size and particle diameter is determined based on the tolerance according to ASTM E-11 for the test sieve of the indicated size. For example, the tolerance for a 50 μm test sieve is 3 μm. Thus, "about 50 μm" means particles with a size between 47 μm and 53 μm. In another example, the tolerance for a 35 μm test sieve is 2.6 μm. Thus, "about 35 μm" means particles with a size between 32.4 μm and 38.6 μm. The ASTM tolerance for a 25 μm sieve is 2.2 μm. For non-standard test sieves (e.g., test sieves less than 20 μm), the indication "about X μm" means ±15% for 5-15 μm and ±50% for less than 5 μm. For example, "about 1 μm" means particles with a size between 0.5-1.5 μm.
[0099] The irregular particulates are flame treated to remelt the surface and form substantially spherical particles. Flame treated irregular particulates can be achieved by flame sphering by introducing appropriately sized irregular particulates into a propane / oxygen flame and directing the flame into a collection system.
[0100] One specific example of substantially spherical microparticles according to the present disclosure is BIC2-MPS glass, which has a glass composition of 0.733 mole fraction SiO2, 0.109 mole fraction Na2O, 0.073 mole fraction BaO, 0.074 mole fraction Ta2O5, and 0.011 mole fraction B2O3. Other specific examples are BIC1-MPS and BIC3-MPS glasses.
[0101] Treating glass microspheres to reduce surface reactivity is well known in the art. The treatment can be accomplished, for example, by contacting the flame-treated microparticles with a CMF-PBS solution at a temperature of 80° C. for at least 72 hours, preferably with stirring at 120 rpm, and washing with ultra-high purity water. The microparticles can be at a concentration of 0.2 g per mL of CMF-PBS. One specific example of a treated microparticle according to the present disclosure is a glass of BIC2-MPC, which has a glass composition of 0.739 mole fraction SiO2, 0.086 mole fraction Na2O, 0.085 mole fraction BaO, 0.085 mole fraction Ta2O5, and 0.006 mole fraction B2O3.
[0102] Spheronizing irregular particulates is not expected to substantially change the diameter of the particles, however, the spheronized particles may be sieved either before or after processing to provide particles of a desired size.
[0103] Imaging Radiopaque glass microspheres according to the present disclosure may be used in X-ray based imaging, such as radiographic imaging, computed tomography (CT) imaging, cone beam CT imaging, or fluoroscopic imaging.
[0104] The desired radiopacity of the glass microspheres may depend on the clinical scenario, such as the type of imaging used, the targeted treatment area, and / or the estimated packing density of the microspheres. A glass with a higher degree of radiopacity may be desirable when a relatively small number of microspheres are being delivered, when the microspheres are expected to be distributed over a relatively large area, when a relatively low-power imaging technique is being used, or any combination thereof. On the other hand, a glass with a lower radiopacity may be desirable when a relatively large number of microspheres are being delivered, when the microspheres are expected to be distributed over a relatively small area, when a relatively high-power imaging technique is being used, or any combination thereof, since too much radiopacity may result in imaging artifacts and reduced imaging quality.
[0105] Less than 45 μm and 2.7 g / cm 3 ~Approx. 4.3g / cm 3 , for example, about 2.9 g / cm 3 ~Approx. 3.7g / cm 3 , or about 3.3 g / cm 3 ~Approx. 3.6g / cm 3 Glass microspheres according to the present disclosure having a density of about 3.3 g / cm may be useful in applications where the microspheres are administered by intra-arterial or intravenous delivery. 3 Glass microspheres according to the present disclosure having a density of approximately 100 nm have substantially the same density as currently commercially available radioactive microparticles.
[0106] Some glass microspheres according to the present disclosure may be compatible with positron emission tomography (PET), single photon emission computed tomography (SPECT), and / or magnetic resonance imaging (MRI), in that the glass microspheres do not affect PET, SPECT, or MRI.
[0107] In imaging applications where glass microspheres are administered to a patient via intra-arterial or intravenous delivery to image the patient's liver, at least about 750 microspheres per gram of liver may be administered to the patient. In some instances, about 1000 to about 5000 microspheres may be administered per gram of liver. In a typical adult patient, about 1 million to about 7 million microspheres may be administered.
[0108] Radiotherapeutic mixtures, compositions, delivery devices, and methods Radioactive microparticles are manufactured in only a few locations and are prepared for delivery to hospitals around the world. The specific activity of the microparticles is calibrated to provide the desired activity at the planned time of administration. For example, TheraSphere yttrium-90 glass microparticles are prepared by neutron activation of yttrium-89-containing glass microparticles to produce microparticles with a nominal specific activity of about 110 GBq / g at calibration, and are typically provided in amounts of about 1.2 million microparticles (about 3 GBq in about 27 mg) to 8 million microparticles (about 20 GBq in about 180 mg) per vial. Depending on the delay between calibration and administration, the amount of effective radioactivity delivered can range from 0.17 GBq (1.2 million microparticles injected 9 days after calibration) to 18 GBq (8 million microparticles injected 1 day after calibration) per vial.
[0109] As mentioned above, it may be desirable to administer more microparticles with lower specific activity for a given amount of radioactivity, since increasing the number of microparticles provides better tumor coverage than administering fewer microparticles with higher specific activity.For example, to administer 3GBq of radioactivity to a patient, administering 6 million microparticles with an overall specific activity of 22GBq / g may provide better tumor coverage than administering 1.5 million microparticles with an overall specific activity of 88GBq / g.
[0110] Without wishing to be bound by theory, the authors of the present disclosure believe that for at least some tumor sizes and / or degrees of vascularization, administering to a patient a mixture of (i) radioactive microparticles and (ii) non-radioactive microparticles according to the present disclosure may provide at least some of the benefits associated with administering more microparticles at a lower specific activity, even if the individual radioactive microparticles are at a higher specific activity.
[0111] The present disclosure provides a mixture of (i) radioactive glass particles and (ii) a non-radioactive radiopaque particulate glass material according to the present disclosure. The radioactive glass particles are suitable for treating tumors in the liver. The radioactive glass particles and the non-radioactive radiopaque particulate glass material have substantially the same size. Particles of substantially the same size are expected to behave substantially the same after injection into a patient. Thus, administering a mixture of particles of substantially the same size is believed to result in a uniform distribution of radioactive and non-radioactive particles.
[0112] In the context of this disclosure, particles having substantially the same size means that the average size of (a) the radioactive microparticles and (b) the radiopaque non-radioactive microparticles is within 40% of the average of these two average sizes. For example, the radioactive microparticles may have an average diameter of 20 μm, while the radiopaque non-radioactive microparticles have an average diameter of 30 μm. A difference of 10 μm between the two types of microparticles is 40% of the average of the two values. The smaller the size difference, the more similar the behavior of the particles is expected. Therefore, it is preferred that the difference in average size is within 10% of the two average sizes.
[0113] The density of the microparticles can also affect the behavior of the microparticles after injection into a patient. In certain instances, the radiopaque microparticles and radioactive glass microparticles of the present disclosure have substantially the same density.
[0114] The term "particle density" refers to the mass of an individual particle per unit volume. This is in contrast to the term "bulk density", which refers to the mass of multiple particles per total volume. Particle density is an inherent property of a material, and bulk density varies depending on the properties of the material in the total volume. Particle density may be discussed in terms of specific gravity, which is the ratio of the density of a material to the density of a standard material. In the context of this disclosure, specific gravity is with respect to water. In the context of this disclosure, particles having substantially the same density refer to particles that are within about 30% of the average, preferably within about 15%.
[0115] The particle densities of (a) the radioactive particles and (b) the radiopaque non-radioactive particles may be within about 30%, preferably within about 15%, of the mean. For example, the radioactive particles have a particle density of 3.3 g / cm 3 while the radiopaque non-radioactive particulate may have a particle density of 3.9 g / cm 3 The particle density between the two types of particulates may be 0.6 g / cm. 3 The difference between the mean of these two values is 16.7%.
[0116] Mixtures according to the present disclosure may be made using any of the radiopaque glass compositions disclosed herein.
[0117] The mixture can be prepared by exposing pre-radioactive glass particulate to neutron radiation to form radioactive glass particulate, and mixing the radioactive glass particulate with the radiopaque particulate glass of the present disclosure.
[0118] In one particular example, the mixture includes (i) substantially spherical radioactive yttrium-aluminosilicate glass particulates comprising about 40% by weight SiO, about 20% by weight AlO, and about 40% by weight YO (corresponding to about 0.170 mole fraction YO, about 0.189 mole fraction AlO, and about 0.641 mole fraction SiO), and (ii) a substantially spherical radiopaque particulate glass material comprising about 0.741 mole fraction SiO, about 0.086 mole fraction NaO, about 0.085 mole fraction BaO, about 0.085 mole fraction TaO, and about 0.006 mole fraction BO.
[0119] Yttrium-89 can be converted to yttrium-90 by exposing the yttrium-89 contained in the particles to a medium flux of ions. The specific activity of the resulting particles depends on the level of flux and the duration of exposure. For example, yttrium-89 is nominally 10 14 Neutrons / cm 2 / sec flux, neutron radiation can act for many days and reach specific activities of over 150 GBq / g.
[0120] Improved tumor coverage, e.g., more uniform microparticle distribution, may be achieved using mixtures having radioactive microparticles in an amount of about 80% to about 10% (w / w) of the total mass of microparticles in the composition. In the context of this disclosure, it should be understood that any reference to improvement is in comparison to the same number of radioactive microparticles in the absence of additional non-radioactive microparticles.
[0121] For radioactive particles having a high specific activity, such as 140 GBq / g, the mixture may have fewer radioactive particles (such as about 10% by mass). In contrast, for radioactive particles having a low specific activity, such as 4 GBq / g, the mixture may have more radioactive particles (such as about 80% by mass). In a particular example, for radioactive particles having a specific activity of, for example, about 88 GBq / g, the mixture may have about 25% by mass of radioactive particles.
[0122] "Specific activity" should be understood to mean the activity per unit mass of a radioactive particle, while "total specific activity" means the activity per unit mass of a mixture of radioactive and non-radioactive particles. For example, if you take 1 gram of radioactive particles with a specific activity of 10 GBq / g and mix these particles with 1 gram of non-radioactive particles, you will get a mixture of particles with an overall specific activity of 5 GBq / g.
[0123] Mixtures of radioactive and non-radioactive particles can be prepared by formulating different numbers of total microparticles with desired radioactivity.The total number of microparticles can be selected based on tumor size and / or degree of vascularization.For example, a formulation with 10GBq radioactivity in 0.5 grams of microparticles may be desirable for treating tumors with a certain degree of vascularization, while a formulation with 10GBq radioactivity in 1 gram may be desirable for treating more vascularized tumors.
[0124] In yet another aspect of the present disclosure, where the mixture includes radioactive glass microspheres, radiation is delivered to the mammal by administering a therapeutic amount of the mixture to the mammal. Such methods may additionally include imaging the mammal using an X-ray based radiation imaging technique. Administration of a therapeutic amount of such a mixture of microparticles to a patient may allow for calculation of the delivered dose of radiation to tissue by the non-imageable radioactive microparticles based on the measured distribution of non-radioactive radiopaque microparticles in the tissue.
[0125] Without wishing to be bound by theory, the authors of the present disclosure further believe that at least some of the advantages of administering a mixture of radioactive and non-radioactive microparticles may be obtained upon separate administration of radioactive and non-radioactive microparticles.
[0126] In some aspects, the present disclosure provides therapeutic or diagnostic compositions comprising a mixture of radioactive and non-radioactive microparticles, where at least some of the non-radioactive microparticles are glass materials disclosed herein.
[0127] The radioactive and non-radioactive microparticles have a difference in particle density that is within 30%, preferably within 15%, of the average of the two particle densities.
[0128] The radioactive microparticles may have an average diameter of about 10 to about 1200 microns, for example, about 20 to about 40 microns. The non-radioactive microparticles may have an average size of about 10 to about 1200 microns, for example, about 20 to about 40 microns. The radioactive and non-radioactive microparticles may have a difference in average size, the difference being within 40% of the average of the two average sizes.
[0129] In some instances, the radioactive and non-radioactive particles have substantially the same resistance when flowed through a liquid through a conduit.
[0130] Those skilled in the art will understand that the resistance of an object to flow in a liquid through a conduit is reflected by a drag coefficient, which is a function of surface friction and form drag. Thus, the resistance of a particulate to flow in a liquid through a conduit can be affected, for example, by the size, surface area, shape, density, and / or surface condition of the particulate. Those skilled in the art will further readily understand that two different particles can have substantially the same resistance, since changing a characteristic to increase drag can be offset by changing another characteristic to decrease drag. For example, if the surface condition of a first particle is sufficiently smoother than the surface condition of a second particle, the two particles can still have substantially the same drag coefficient, even if the first particle is larger than the second particle.
[0131] In the context of this disclosure, the time it takes for a bolus of particles to fall a set distance through a liquid may represent the resistance of the particles to flow through the liquid through a conduit. This time can be measured by filling a transparent column filled with distilled water with a known number of particles. The number of particles should be selected so that the height of the bolus of particles is 2-5 times the inner diameter of the column. Once the particles have settled to the bottom of the column, the column is inverted and the particles fall into the distilled water by a drag force against gravity. The total time it takes for the particles to fall through a transition point is measured. The transition point is measured from the apex of the bolus of particles and is at least 100 times the inner diameter of the column. For example, in a column with an inner diameter of 0.5 cm, the settled particles may be 1.5 cm high, and the total time it takes for the bolus of particles to fall is the time it takes for all the particles to fall through a point 50 cm away from the apex of the settled particles.
[0132] This total fall time is compared to the total fall time of a substantially equal number of different particle populations tested under the same conditions (i.e., same liquid, same column, same transition point). The relative drag ratio is calculated by dividing the fall time of the first particle population by the fall time of the second particle population. In the context of the present disclosure, the first and second particle populations are considered to have substantially the same resistance to flow through a liquid passing through a conduit when the relative drag ratio is between about 0.95:1 and about 1:0.95.
[0133] In some examples, the radioactive microparticles comprise from about 10% to about 80%, for example about 25%, based on the total weight of the microparticles in the composition.
[0134] In some instances, the radioactive microparticle is a diagnostic radioactive microparticle. In some instances, the radioactive microparticle is a therapeutic radioactive microparticle.
[0135] The diagnostic radioactive microparticles may comprise one or more radioisotopes selected from the group consisting of copper-67, holmium-166, indium-111, iodine-131, lutetium-177, molybdenum-99, phosphorus-32, rubidium-82, technetium-99m, and thallium-201.
[0136] The therapeutic radioactive microparticles may comprise one or more radioisotopes selected from the group consisting of Actinium-225, Bismuth-213, Copper-67, Indium-111, Iodine-131, Iodine-125, Gadolinium-157, Holmium-166, Lead-212, Lutetium-177, Palladium-103, Phosphorus-32, Radium-223, Rhenium-186, Rhenium-188, Samarium-153, Strontium-89, and Tungsten-188.
[0137] The radioactive glass particles may be substantially spherical. The non-radioactive particles may be substantially spherical.
[0138] In another aspect, the present disclosure provides a method comprising administering to a patient a mixture of radioactive and non-radioactive microparticles as described above, wherein the administration is by intravascular, intraperitoneal, or transdermal delivery.
[0139] In yet another aspect, the present disclosure provides a delivery device for intravascular, intraperitoneal, or transdermal delivery of a mixture of radioactive and non-radioactive microparticles to a patient. The delivery device includes a fluid inlet fluidly connectable to the mixed transport medium, a fluid outlet, a fluid mixer fluidly connected to the fluid inlet and the fluid outlet, a radioactive microparticle source fluidly connected to the fluid mixer, and a non-radioactive microparticle source fluidly connected to the fluid mixer. The radioactive microparticle source is distinct from the non-radioactive microparticle source. The fluid mixer mixes the radioactive and non-radioactive microparticles and utilizes the mixed transport medium to deliver the mixture of radioactive and non-radioactive microparticles from the fluid outlet. At least some of the non-radioactive microparticles are comprised of a glass material according to the present disclosure.
[0140] In yet another aspect, the present disclosure provides a delivery device for intravascular, intraperitoneal, or transdermal delivery of a mixture of radioactive and non-radioactive microparticles to a patient. The delivery device includes at least one fluid inlet fluidly connectable to a transport medium, a radioactive microparticle source fluidly connected to the at least one fluid inlet, a non-radioactive microparticle source fluidly connected to the at least one fluid inlet, a first fluid outlet fluidly connected to the radioactive microparticle source, and a second fluid outlet fluidly connected to the non-radioactive microparticle source. The radioactive microparticle source is distinct from the non-radioactive microparticle source. At least some of the non-radioactive microparticles are comprised of a glass material according to the present disclosure. In some examples, the delivery device delivers the radioactive and non-radioactive microparticles in a single treatment session. In some examples, the first and second fluid outlets are proximate to each other. In the context of the present disclosure, the fluid outlets should be understood to be proximate to each other when the radioactive and non-radioactive microparticles can be administered to the patient substantially simultaneously, for example, during the course of a single treatment session.
[0141] The radioactive microparticles in the delivery device can be any radioactive microparticles disclosed herein. The non-radioactive microparticles in the delivery device can be any non-radioactive microparticles disclosed herein. In some examples, the radioactive microparticles comprise about 10% to about 80%, e.g., about 25%, of the total mass of the microparticles in the delivery device.
[0142] In yet another aspect, the present disclosure provides a method comprising mixing (i) a first population of radioactive microparticles and (ii) a second population of non-radioactive microparticles and administering to a patient an appropriate amount of the mixture for therapeutic or diagnostic use. At least some of the non-radioactive microparticles are comprised of a glass material according to the present disclosure. The radioactive microparticles used in the method may be any of the radioactive microparticles disclosed herein. The non-radioactive microparticles used in the method may be any of the non-radioactive microparticles disclosed herein. In some examples, the radioactive microparticles comprise about 10% to about 80%, e.g., about 25%, based on the total mass of the microparticles used in the method. Administration can be by intravascular, intraperitoneal, or transdermal delivery.
[0143] In another aspect, the present disclosure provides a method of administering a suitable amount of microparticles to a patient for therapeutic or diagnostic use. The method includes either administering non-radioactive microparticles to the patient and administering radioactive microparticles to the patient without first detecting the non-radioactive microparticles, or administering radioactive microparticles to the patient and administering non-radioactive microparticles to the patient without first detecting the radioactive microparticles. At least some of the non-radioactive microparticles are comprised of a glass material according to the present disclosure. The administration is by intravascular, intraperitoneal, or transdermal delivery. The route of administration of the non-radioactive microparticles is the same as the route of administration of the radioactive microparticles.
[0144] In some examples, the methods include simultaneous administration of non-radioactive and radioactive microparticles, hi other examples, the methods include sequential administration of non-radioactive and radioactive microparticles, or sequential administration of radioactive and non-radioactive particles.
[0145] In yet another aspect, the present disclosure provides a method of administering a suitable amount of microparticles for therapeutic or diagnostic use, the method comprising simultaneously administering to a patient (i) a first population of radioactive microparticles, and (ii) a second population of non-radioactive microparticles, at least some of which are comprised of a glass material according to the present disclosure.
[0146] In some instances, the first population of radioactive microparticles is distinct from the second population of non-radioactive microparticles. The first population of radioactive microparticles and the second population of non-radioactive microparticles can be administered as a mixture.
[0147] In yet another aspect, the present disclosure provides a method of administering a suitable amount of microparticles for therapeutic or diagnostic purposes, the method comprising sequentially administering non-radioactive and radioactive microparticles to a patient in a single treatment session, at least some of the non-radioactive microparticles being comprised of a glass material according to the present disclosure.
[0148] In yet another aspect, the present disclosure provides a method comprising sequentially administering to a patient (i) therapeutic radioactive microparticles and then (ii) non-radioactive microparticles, at least some of which are comprised of a glass material according to the present disclosure.
[0149] In some instances, the sequential administration includes intermittent administration of non-radioactive and radioactive microparticles. The intermittent administration can include alternating administration of radioactive and radioactive microparticles.
[0150] In some instances, sequential administration involves administration of all of one type of microparticles before administration of the next type of microparticles. For example, sequential administration can involve administration of all of the non-radioactive microparticles before administration of any of the radioactive microparticles, or administration of all of the radioactive microparticles before administration of any of the non-radioactive microparticles.
[0151] Methods according to the present disclosure may allow for the delivery of therapeutically appropriate amounts of radiation to a patient, or for the delivery of diagnostically appropriate amounts of non-radioactive microparticles to a patient.
[0152] In the methods of the present disclosure, administration can be by intravascular, intraperitoneal, or transdermal delivery, and the radioactive and / or non-radioactive microparticles can be as described above, and about 10% to about 80%, e.g., about 25%, of the total mass of microparticles delivered can be radioactive microparticles, or any combination thereof.
[0153] While the above description relates to methods of administering radioactive and non-radioactive microparticles, the present disclosure likewise contemplates corresponding "uses" of microparticles, including microparticles useful in the disclosed methods, and the use of microparticles in the manufacture of administrable formulations useful in the disclosed methods.
[0154] In the context of the present disclosure, it should be understood that the non-radioactive particulates discussed in this section of the present disclosure may have one or a combination of the characteristics of any of the glass materials discussed above in the section entitled "Glass Materials." For example, the non-radioactive particulates may have any or all of the characteristics associated with the microparticles, microspheres, glass microspheres, or spherical particles described above.
[0155] In the context of this disclosure, it should be understood that the radioactive microparticles discussed in this section of the disclosure can have one or a combination of the characteristics of any of the radioactive glass materials discussed in this disclosure.
[0156] Working Example
[0157] Synthesis of irregular glass powders and microspheres. Various glasses were synthesized according to the present disclosure. The theoretical compositions of the TRCR# and BIC# glasses are shown in Table 1 above. In addition, a comparative glass COMP# was also synthesized. The theoretical compositions of these comparative examples are shown in Table 3. [Table 3]
[0158] The density of the irregular particulate glass material sieved to collect particles 45 μm or smaller, the density of the substantially spherical particulate glass material, and the radiopacity of the substantially spherical glass composition are shown in Table 4. [Table 4]
[0159] Comparative Example "COMP1" corresponds to YAS4 disclosed in U.S. Patent No. 4,789,501. Due to the clinical usefulness of this glass and known composition-structure-property relationships, the authors of the present disclosure used this comparative example to identify glass compositions having substantially equivalent microsphere density (±10%), enhanced radiopacity, acceptable in vitro cytotoxicity, acceptable hemocompatibility, and / or acceptable genotoxicity. Without being bound by theory, the authors of the present disclosure expect that glass compositions meeting many or all of these requirements will be useful for applications in transarterial radioembolization.
[0160] For glass synthesis, analytical grade reagents were weighed according to the theoretical compositions outlined in Tables 1 and 3. After uniform blending for at least 1 hour, the reagents were placed into platinum-rhodium crucibles (50cc-200cc) and fired (1500°C-1600°C, 3-5 hours) using an electric furnace (Carbolite Furnaces, Sheffield, UK), then diluted with water for injection (USP, Ph. Eur. Grade, The mixture was shock quenched in a 50 mL flask (Rocky Mountain Biologics, MT, US). The resulting irregular glass powder was dried overnight in an oven (120 °C).
[0161] All of the exemplary glasses of the present disclosure, as well as COMP1 and COMP3, readily melted and provided a non-viscous fluid prior to shock quenching. The COMP2 glass did not melt, phase separated, or provided a viscous fluid.
[0162] Irregular glass powders from the various melts were mixed together and milled as one lot using a planetary ball mill with ZrO2 grinding media. The resulting crushed irregular glass powder was sieved to collect particles smaller than 45 μm.
[0163] The properly classified irregular glass powder was then introduced into a propane / oxygen flame with properly controlled oxygen and propane flows. The material was remelted and spherical granules were formed by surface tension in a process otherwise known as spheronization. The burner flame was directed towards a stainless steel collection system which collected the glass microspheres as they were released from the flame. The glass microspheres were then sieved to obtain microspheres with an average size range of 20 μm to 30 μm.
[0164] X-ray diffraction X-ray diffraction (XRD) measurements of the irregular glass powders and / or particulates were carried out using a Bruker D2 Phaser diffractometer (Bruker AXS Inc., Madison, WI) equipped with a Cu target X-ray tube coupled to an X-ray generator (30 kV; 10 mA). Samples of each experimental material were prepared by pressing the irregular glass powder or particulates into a hollow zero background holder. Powder diffraction powders were acquired in the scan angle range of 10°<2θ<100° with a step size of 0.02°. The collection time for the XRD spectra was 4930 s.
[0165] Helium pycnometry The density of the irregular glass powder and / or microparticles was measured using helium pycnometry (AccuPyc II 1340, Micromeritics) using the mean value (± standard deviation SD) of 10 to 60 measurements recorded on the quenched material for the irregular glass powder morphology and the mean value of 10 measurements (± SD) for the final microparticle morphology.
[0166] Differential scanning calorimetry The thermal properties of the irregular glass powders were characterized by a Netzsch Pegasus F404 differential scanning calorimeter (DSC, Burlington, MA). DSC measurements were performed from ambient temperature to 1000 °C at a heating rate of 10 °C / min, and the onset (Tg, onset) and midpoint (Tg, midpoint) glass transition temperatures were determined graphically using Proteus 6.0 software. The DSC used in this study has a tolerance of 2%.
[0167] Microsphere Processing To obtain a substantially smooth surface that is substantially free of any surface reaction deposits resulting from spheronization, the flame-treated microspheres were subjected to post-spheronization processing by extracting them in calcium- and magnesium-free phosphate buffer solution (CMF-PBS, product code: MT21040CV, Corning™, NY, US) at a rate of 0.2 g / mL.
[0168] In the first experiment, the microspheres were extracted in a closed vessel in a shaking water bath at 50° C. for 72±2 hours, 120±2 hours, 240±2 hours, 288±2 hours, and 360±2 hours under continuous agitation at 120 rpm. Further analysis was then completed by extracting the microspheres in a closed vessel under accelerated conditions (80° C.) in a shaking water bath for 24±2 hours and 72±2 hours under continuous agitation at 120 rpm to explore the possibility of facilitating the processing steps designed for manufacturing.
[0169] After extraction, the microparticles were separated from the CMF-PBS, washed (10 times) with sterile water for injection (USP, Ph. Eur. grade, Rocky Mountain Biologics, MT, US), and then dried at 120±2°C until constant weight (mass difference ≦0.1%).
[0170] The glass microspheres were then stored for analysis or regrinding and were size screened to ensure a final average microparticle size of 20 μm to 30 μm before being packaged into cleaned glass storage vials for bulk storage.
[0171] Microsphere cleanliness (i.e., substantially free of surface reaction deposits and / or contaminants by visual inspection) was confirmed by scanning electron microscope (SEM) analysis. Extracts of particulates obtained during the abovementioned 72±2 h, 120±2 h, 240±2 h, 288±2 h, and 360±2 h treatment studies were analyzed for the concentrations of Si, Na, Ta, B, and Ba elements by ICP-OES using a validated test protocol at an ISO 17025 accredited laboratory (NSL Analytical, 4450 Cranwood Pkwy, Warrensville Heights, OH, US).
[0172] Composition analysis For compositional analysis, the irregular glass powders and / or microspheres were subjected to sample preparation by fusion / microwave acid digestion and analyzed by ICP-OES using a validated test protocol in an ISO17025 accredited laboratory (NSL Analytical, 450 Cranwood Pkwy, Warrensville Heights, OH, USA).
[0173] Scanning electron microscope The morphology of the carbon-coated irregular glass powders and / or microspheres was investigated using a Hitachi S-4700 field emission SEM (FE-SEM) operating at an accelerating voltage of 1.5 KV to 10.0 KV, an emission current of about 15 μA to 22 μA, and a working distance of about 12 mm to 14 mm, and SEM images were obtained at magnifications of 250x and 1000x.
[0174] Safety evaluation of axial computed tomography (CT) scans and MRI The CT radiopacity of bulk microspheres was evaluated by quantitative radiopacity measurements, expressed as Hounsfield units (HU) obtained from five repeated regions of significance (ROL, n=5) recorded from each axial CT scan (1 mm slice thickness, pitch=0.5, 70 kVp and 120 kVp) using a 1.2 mL glass v-vial (product code: Z115061, Sigma Aldrich, Canada) containing 500 mg of microparticles in 6 μL of sterile saline. All measurements were performed on experimental material with a mean diameter (±SD) in the range of 20 μm to 30 μm, using a Siemens Somatom Definition AS+ scanner (Siemens Healthcare, Erlangen, Germany) and the extended HU range option used for scanning.
[0175] To investigate the effect of microsphere concentration on quantitative CT radiopacity and MRI safety, microspheres of BIC1-BIC3 and COMP1 control were prepared (in triplicate) at five different concentrations (at the following volume fractions: 1.25%, 2.5%, 5%, 7.5%, and 10%). A gel-only tube (0%) was also used as a baseline control. All volume fractions were calculated using the microsphere densities in Tables 2 and 4 and prepared in 1.5 mL of 8% gelatin. Microspheres were added to vigorously shaken gelatin in 5 mm NMR tubes to optimize the uniformity of microsphere distribution, then quickly set on ice. If the tube was too heterogeneous, the gel was melted and the microspheres were redispersed, followed by resetting with ice. Depending on the microsphere density, some clumps of microspheres formed around the periphery and at the bottom of the tube.
[0176] CT data were acquired at 80 kVp with a sample resolution of 100 μm using a Trifoil Preclinical PET / CT scanner, and all CT images were converted to HU for subsequent analysis. MRI data were acquired on a 3T Varian MRI system using an INOVA console. Bulk T1, T2, and T2 *For quantitative measurements, a birdcage RF transmit / receive coil was used, and the tube was positioned so that the bulk of the microspheres fell within the imaging field of the coil, while bulk measurements were limited to the portion of the tube that was not confined to a single slice within the coil. Qualitative MRI measurements were performed using a standard gradient echo sequence (T2 * The data were also acquired using a short TR anatomical localizer scan (T1-weighted), spin-echo sequence (T2-weighted), and a short TR anatomical localizer scan (T1-weighted). To improve scientific comparisons, all quantitative parameters were calculated using R1, R2, or R2 weighting. * Note that the relaxation rate (R) is inversely proportional to the time decay constant (T), where R1 is 1 / T1, R2 is 1 / T2, and R2 is 1 / T3. * is 1 / T2 * It is.
[0177] Next, CT radiopacity, R1 relaxivity, R2 relaxivity, R2 * Five image characteristics were assessed: relaxivity, magnetic susceptibility, and chromatic aberration. For each characteristic, for example, R1 (or R2, etc.) for each tube was measured and compared to a control gel tube, and delta (D)R1 was calculated. DR1 was then graphed against volume fraction for each set of tubes, and a linear regression line was plotted.
[0178] In vitro cytotoxicity The biological reactivity of mammalian cell monolayers, L929 mouse fibroblast cells, in response to experimental materials. Determined in accordance with ISO 10993-5:2009, Biological evaluation of medical devices-Part 5: in vitro cytotoxicity testing employing a validated biocompatibility laboratory (Toxikon Corporation, Bedford, MA, and Nelson Labs, Salt Lake City, UT, US).
[0179] Experimental materials were prepared according to ISO10993-12: 2012, Biological evaluation of medical devices - Part 12: Sample preparation and reference materials, employing an extraction ratio of 0.2 g / mL mass / volume. Positive (natural rubber) and negative (plastic) control materials were prepared to verify the functionality of the test system.
[0180] Experimental and control extracts were used to replace the maintenance medium of cell cultures. Experimental extracts were tested at serial dilutions of 100% (NEAT), 50%, 25%, and 12.5% in serum-supplemented (complete) minimum essential medium (MEM) with and without 5% bovine serum (1XMEM5).
[0181] All cultures were incubated at 37 ± 1°C in a humidified atmosphere containing 5 ± 1% CO2 for 24 ± 2 h (for untreated microspheres during initial screening) or 72 ± 2 h (for treated microspheres that facilitated microsphere optimization) in at least six replicates.
[0182] The viability of cells after exposure to the extract was measured by their ability to take up a vital dye, MTT reagent. The dye was added to the cells and actively taken up by viable cells. The number of viable cells correlated with the color intensity as determined by photometric measurement at 570 nm after the extract.
[0183] In vitro genotoxicity This study was conducted to partially fulfill the requirements of ISO 10993-3:2014, "Biological evaluation of medical devices - Part 3: Testing for genotoxicity, carcinogenicity, and reproductive toxicity" and the Organization for Economic Cooperation and Development (OECD) 471 and Guidelines for Testing of Chemicals, "Bacterial reverse mutation test using an accredited biocompatibility testing laboratory (NAMSA Corporation, Northwood, OH, US)."
[0184] Test substances, controls, and experimental blanks (extraction solvent without test substance) were prepared according to ISO10993-12:2012 "Biological evaluation of medical devices - Part 12: Sample preparation and reference materials in DMSO and saline at 50°C for 72 hours under continuous stirring" employing a mass / volume extraction ratio of 0.2 g / mL. After extraction, all extracts were visually inspected for color, turbidity, and particulates and kept at room temperature for less than 3 hours before use. Extracts were not centrifuged, filtered, or subjected to other alternative methods. Prior to dosing and testing, test strain cultures (Salmonella typhimurium test strains TA98, TA100, TA1535, and TA1537, and E. coli test strain WP2uvrA) were checked for genetic markers.
[0185] Following this, the molten top agar was supplemented with histidine-biotin or tryptophan solutions of the S. typhimurium or E. coli test strains, respectively. This supplementation caused the bacteria on the plates to undergo several divisions forming a background flora that could be examined with a darkfield colony counter and was visible to the naked eye. Separate test tubes containing 2.0 mL of molten top agar were inoculated with 0.1 mL cultures of each of the five test strains and 0.1 mL DMSO or saline test article extracts. A 0.5 mL aliquot of sterile water for injection or S9 homogenate was added as required to provide metabolic activation. This mixture was poured onto three plates of minimal E medium labeled with the test number, the appropriate test strain, and the S9 metabolic activation system (if applicable). Each negative control and six positive controls were also tested in parallel. Histidine-free media plates (for Salmonella typhimurium) and tryptophan-free media plates (for E. coli) were prepared in triplicate as follows. DMSO and saline test article extracts with and without I.S9 activity II. Negative controls with and without S9 activity III. Benzo[a]pyrene in the Presence of S9 and 2-Nitrofluorene in the Presence of S9 Activity with TA98 Strain IV. 2-Aminoanthracene in the Presence of S9 and Sodium Azide in the Absence of S9 Activity with TA100 Strain V. 2-aminoanthracene in the presence of S9 and sodium azide in the absence of S9 activity with strain TA1535 VI. 2-Aminoanthracene in the Presence of S9 and ICR-191 in the Absence of S9 Activity with TA1537 Strain VII. 2-Aminoanthracene in the Presence of S9 and MMS in the Absence of S9 Activity with WP2uwA
[0186] The plates were incubated at 37° C. for 2 days. After the incubation period, the revertant colonies on each plate were recorded by the mean number of revertants and the calculated standard deviation. For each strain tested, the mean number of revertants on the test plates was then compared with the mean number of revertants on the negative control plates, and the characteristics of the background flora were also recorded.
[0187] In vitro hemocompatibility The procedure employs the principles outlined in ASTM F756:2017. The ASTM method has been validated in accordance with ISO10993-4:2017, "Biological Evaluation of Medical Devices - Part 3: Selection of Tests for Interactions with Blood" using certified biocompatibility laboratories (Nelson Labs, Salt Lake City, UT and Nelson Labs LLC, Salt Lake City, UT) and in compliance with U.S. FDA GMP regulations 21 CFR parts 210, 211 and 820 without any deviation from the procedure. Testing followed the principles outlined in ASTM F756:2017, using calcium and magnesium free PBS as the extraction solvent, and validating the ASTM method using citrated human blood in accordance with ISO10993-4:2017 (which states that due to differences in blood activity, human blood should be used when possible).
[0188] For blood collection, equal amounts of blood from three donors were collected in vacutainers containing 0.1 M sodium citrate (3.2% anticoagulant to blood) in a 9:1 ratio. The collected blood was refrigerated until blood tests were performed, pooled, and used for testing within 4 hours of collection. Hemoglobin standards were diluted with Drabkin's reagent to obtain solutions with concentrations of 0.80, 0.60, 0.40, 0.30, 0.20, 0.10, 0.02, and 0.01 mg / mL. These solutions were left to stand at room temperature for a minimum of 15 minutes, and the absorbance was read on a spectrophotometer at 540 nanometers (nm). A standard curve was then determined using linear regression of hemoglobin absorbance values and standard concentrations. To measure plasma hemoglobin, blood was centrifuged at 700-800 × g for 15 minutes. A 1 mL aliquot of plasma was then added to 1 mL of Drabkin's reagent and allowed to stand at room temperature for a minimum of 15 minutes before the absorbance was read on a spectrophotometer at 540 nm. Plasma free hemoglobin concentration was determined by determining hemoglobin concentration from the standard curve and multiplying by a factor of 2 (confirmed to be less than 2 mg / mL). The amount of total hemoglobin present was measured in duplicate by adding a 20 μL aliquot of blood to 5 mL of Drabkin's reagent and allowing the solution to stand at room temperature for a minimum of 15 minutes before reading the absorbance on a spectrophotometer at 540 nm. Hemoglobin concentration was then determined from the standard curve and multiplied by a factor of 251 to account for dilution. Based on the total hemoglobin present, blood was diluted to 10±1 mg / mL in CMF-PBS. To verify the dilution of blood, 300 μL aliquots of diluted blood were added to 4.5 mL of Drabkin's reagent in triplicate and allowed to sit at room temperature for a minimum of 15 minutes before reading the absorbance in a spectrophotometer at a wavelength of 540 nm. Hemoglobin concentrations were then determined from the standard curve and multiplied by a factor of 16 to account for the dilution.
[0189] Positive controls (hemolytic), negative controls (non-hemolytic), and blanks of experimental materials were prepared using a mass / volume ratio of 0.2 g / mL or 6 cm 2The samples were prepared using a surface area / extraction volume of 1 mL / mL, which is in accordance with ISO10993-12:2012 "Biological evaluation of medical devices - Part 12: Sample preparation and reference materials" and samples for indirect contact (extract) analysis were prepared in CMF-PBS at 50 ± 2 °C (agitation) for 72 ± 2 hours. For both the indirect contact (extract) and direct contact methods, appropriate concentrations of extracts or materials were added to labeled glass tubes, prepared in triplicate, and 1 mL of diluted blood was added to each. The glass tubes were then incubated at 37 ± 2 °C for a minimum of 3 hours, gently inverting twice at 30-minute intervals throughout the incubation period. After incubation, the test and control substances were centrifuged at 700-800 × g for 15 minutes, and 1 mL of the supernatant was mixed with 1 mL of Drabkin's reagent and left at room temperature for a minimum of 15 minutes. After centrifugation, the test substances, blanks, and controls were visually inspected for color, turbidity, and particulates in each supernatant. All test and control articles were then read on a spectrophotometer at 540 nm.
[0190] The hemolysis index (% hemolysis) was expressed using the following formula: Hemolysis index = released hemoglobin (mg / mL) / present hemoglobin (mg / mL) x 100 Hemoglobin released (mg / mL) = (optical density x coefficient X + constant) x 16 Hemoglobin present (mg / mL) = diluted blood 10 ± 1 mg / mL
[0191] Corrected hemolytic indices were calculated by subtracting the hemolytic index of the CMF-PBS blank from the hemolytic indices of the test and control substances, and the test substances were compared with the negative control by subtracting the hemolytic index of the negative control from the hemolytic index of the test substance.
[0192] statistical analysis CT and MRI measurements, expressed as the mean (±standard error of the mean, SEM) of three replicates, were subjected to linear regression analysis for each microsphere formulation prepared at various volume fractions, statistically evaluated to ensure that it was non-zero, and further compared with other formulations using Prism 8.0 software (GraphPad. Software Inc., San Diego, CA, US). The significance level was set at p<0.05.
[0193] Amorphous morphology, density, and glass transition temperature The glasses of the examples of the present disclosure and the glasses of the comparative examples were evaluated for amorphous morphology, density, and glass transition temperature in the form of irregular glass powder and microspheres. Regardless of the heat treatment (spheronization) after the preparation of the irregular glass powder, all samples remained amorphous and no identifiable crystalline peaks were detected in any of the formulations evaluated. Table 5 shows the density, Tg (midpoint TgM and inflection point TgI) for the glasses of the comparative examples and the glasses of the examples of the present disclosure in both the irregular glass powder and the microspheres formed after spheronization. [Table 5]
[0194] The density of the commercially available control "COMP1" is approximately 3.3 g / cm 3 The TRCR glass series provided densities of up to 3.05 g / cm3 with only minor variations between the irregular glass powder and microsphere morphologies. In summary, the TRCR glass series provided densities of up to 3.05 g / cm3. 3 (TRCR20) is 4.2674g / cm 3 The TRCR formulations provided a wide range of densities up to 3.1 g / cm3 (TRCR23) and similarly no significant differences were observed between the irregular glass powder and particulate morphologies of each of the formulations. In examining the TRCR formulations themselves, a trend was observed for the density of the flit and microspheres to increase with increasing amounts of Ta2O5 in the glass network. The BIC formulations showed a similar trend in density between the irregular glass powder and microsphere morphologies (3.459 g / cm3, respectively). 3~3.542g / cm 3 and 3.4326 g / cm 3 ~3.5739g / cm 3 ).
[0195] In the analysis of glass transition temperatures, the commercial control consisted of data points between 909°C (TgM) and 915°C (TgI), whereas the TRCR and BIC glass series exhibited a wide range of TgM and TgI data points between 512°C - 794°C and 513°C - 799°C.
[0196] Consideration of processing Figure 1 shows the cumulative ion release curves obtained for BIC2 microspheres (post-spheronization) extracted at 0.2 g / mL in CMF-PBS over 360 h (maintained at 50 °C under continuous stirring (120 rpm)). In summary, Ba was the only element recorded below the ICP-OES detection limit (10 ppm) after the 72 h extraction phase, while B, Ta, Na, and Si were detected at 20 ppm, 30 ppm, 500 ppm, and 430 ppm-440 ppm, respectively. Exhaustive extraction (reported below the ICP-OES detection limit (10 ppm)) was confirmed for all remaining elements over the subsequent 120 h extraction time window, with the exception of Si (530 ppm-540 ppm), which was then shown to reach exhaustive extraction between 240 h and 360 h.
[0197] Chemical analysis and surface morphology Table 6 shows the variation in chemical composition comparing the formulations of COMP1 item and BIC used as feed material for spheronization (irregular glass powder) and the recovered microspheres after spheronization (the same lot was processed for each formulation).
[0198] In summary, all three BIC formulations were observed to have a significant volatilization of alkali elements after spheronization, with a significant decrease in Na2O concentration (in terms of mass% reported by external testing laboratories) up to half of the starting composition of the feed (from 10.05 to 7.84 mass% (BIC1), 14.60 to 7.03 mass% (BIC2), and 10.95 to 5.36 mass% (BIC3)). Congruently, the other element concentrations (i.e., Ta2O5 and / or SiO2) were observed to compensate for the relative loss by a clear increase in the concentration of these elements after spheronization. In addition to this, BIC3 showed a clear volatilization of B2O3 due to spheronization, resulting in a significant decrease in B2O3 concentration (from 3.62 to 1.12 mass%). In contrast, when used as a feedstock, the COMP1 item (Table) remained compositionally unchanged (i.e., within ±3% by weight of the acceptable range between each elemental component).
[0199] The surface morphology of the feed material is shown in Figure 2A and compared to that of the microspheres after spheronization (Figure 2B). SEM images collected as well as the spheronized material show the buildup of surface reaction deposits on the microspheres, which can be attributed to (I) the accumulation of surface deposits due to glass reactions in the gas environment, and / or (II) contamination by debris from the glass manufacturing process or particles in the air or on product contact surfaces.
[0200] Table 7 shows the variation in chemical composition obtained processing a microsphere lot of BIC2 isolated after 360 hours, reaching a thorough extraction of Na2O from the glass network as a result of the aqueous environment, as shown above in Figure 1. The reduction in Na2O as a result of this processing step compared to spheronization is not extensive (7.03% to 5.36% by weight vs. 14.60% to 7.03% by weight, respectively) and can be mainly attributed to the processing step removing unbound surface reaction deposits prior to the time frame evaluated for the first extraction (72 hours), with minimal leaching of Na2O from the glass network here.
[0201] Leveraging the findings of this study, further extraction analysis (for process optimization) was performed with accelerated extraction temperature and shortened time frame to 24 hours (all other variables such as extraction ratio, temperature, and agitation speed remained unchanged) to confirm whether microspheres without surface reaction deposits could be observed by SEM. Figure 2C shows microspheres treated at 80°C for 24 hours, providing near complete removal of surface reaction deposits and / or contaminants observed immediately after spheronization (Figure 2B), whereas microspheres treated at 80°C for 72 hours and resieved after spheronization clearly show complete removal of surface reaction deposits (Figure 2D). BIC2 microspheres treated after 24 and 72 hours were then stored for biocompatibility evaluation. [Table 6] [Table 7]
[0202] CT radiopaque The glass compositions of the examples in Table 1 provide enhanced radiopacity at clinically relevant tube potentials (120 kVp) compared to the control article (COMP1: 5,952 ± 180 HU). Benchtop CT radiopacity was observed to range from 9,978 ± 579 HU (TRCR8) to 21,858 ± 1037 HU (TRCR23). The densities of TRCR3, 8 and 13 are 10% of the density of the comparative article COMP1, and their radiopacity was observed to range from 9,978 ± 579 HU (TRCR8) to 16,374 ± 465 HU (TRCR13).
[0203] BIC1, BIC2, and BIC3 had densities within the desired target range comparable to the control item COMP1, and demonstrated radiopacities ranging from 13,676±642 HU to 16,952±205 HU.
[0204] Regarding the evaluation of CT radiopacity due to the variation in the concentration of microspheres of BIC1 to BIC3 compared to the control item, Figure 3 shows the increase in radiopacity with increasing concentration (volume fraction) of microspheres for the prepared samples with various volume fractions at 80 kVp. Furthermore, there exists a good correlation between the obtained HU values and the volume fraction of microspheres, which indicates that the slope and R 2 The values were as follows (low to high CT radiopacity): COMP1 (R 2 = 0.9739, 287.2), BIC3(R 2 = 0.9465 = 357.9), BIC1(R 2 = 0.9994, 394.5), and BIC2 (R 2 = 0.9742 and 407.7). The data support BIC1 through BIC3 as promising candidate materials offering enhanced radiopacity compared to the COMP1 item at concentrations of microspheres expected to be administered therapeutically.
[0205] MRI evaluation Microsphere formulations BIC1-BIC3 and the COMP1 item are not expected to produce large T1 contrast effects, as supported by the calibration curves shown in Figure 4, which were constructed for R1 relaxivity. The calibration curves show a significant correlation between R1 relaxivity and the concentration of microspheres. Although the slopes, ranging from 0.007 (COMP1) to 0.034 (BIC3), are not statistically zero (p<0.002), the slopes are so small that these microsphere formulations are not expected to produce detectable T1 differences. This is also supported by Figure 5, where no changes in T1 contrast are evident in the tube images.
[0206] Similarly, microsphere formulations BIC1-BIC3 or the COMP1 item are not expected to produce significant T2 contrast effects, as supported by the calibration curves shown in Figure 6 constructed for R2 relaxivity. The calibration curves show a significant correlation between R2 relaxivity and microsphere concentration. Although the slopes ranging from 0.068 (COMP1) to 0.688 (BIC3) are not statistically zero (p<0.003), the slopes are very small, so these formulations do not produce significant differences in signal contrast compared to physiological differences. This is also shown in Figure 5, where there is a very mild T2 contrast change in the highest BIC2 microsphere concentration images.
[0207] R2 * For relaxivity measurements, a calibration curve is shown in Figure 7. The microsphere formulations were designed to achieve a T2 * However, the target location of the microspheres in the vasculature (significant T2 contrast due to blood) * Considering that the contrast change is related to clinical T2 * It is unlikely that this will be sufficient to induce significant changes in the weighted scans. * The slope of the relaxivity was statistically different from zero (p<0.04), with a slope of 3.5s -1 ~6.3s -1 As shown in Figure 5, at the highest microsphere concentration in the control article, the visible T2 * There is a perceptible difference in contrast, relatively few in the BIC2 microspheres, and some air bubbles are visible.
[0208] The local magnetic dose (LMD) obtained from the MRI susceptometry results (shown in Figure 8) shows that the BIC1 through BIC3 microsphere formulations have similar small negative slopes (-0.0074 to -0.0190), indicating that these materials are slightly diamagnetic. This is in contrast to the COMP1 item, which produces a small positive slope (0.0264) and is classified as slightly paramagnetic. BIC1 did not observe statistical significance from 0 (i.e., neutral susceptibility), whereas BIC2, BIC3, and YAS4 all observed statistical significance from non-zero (p<0.04).
[0209] To support the MRI safety of the BIC1, BIC2, and BIC3 microsphere formulations, the following issues were considered: (I) magnetically induced displacement torque, (II) magnetically induced displacement force, and (III) RF-induced tissue heating of tissue around the device.
[0210] Magnetically Induced Displacement Torque Medical devices may exhibit displacement forces and / or rotational torque due to the interaction of the device's magnetic moment with the main static magnetic field of the MRI system. Rotational torque is the tendency in asymmetrically shaped devices that are magnetized in a given direction, with the direction of the magnetic moment aligned with the direction of the main magnetic field. Magnetized microspheres, such as the BIC and COMP1 microsphere formulations, are symmetrically shaped and have no ability to generate torque. Torque is calculated from the vector product of the device magnetic moment (μ) and the main static MRI magnetic field (B0). Metal oxides composed of transition metals, such as the BIC and COMP1 microsphere formulations, classified as magnetic materials, may exhibit either paramagnetism or diamagnetism. These materials have no magnetic moment until placed in an external magnetic field, and the induced magnetic moment is either aligned (paramagnetic) or completely opposed (diamagnetic) to the direction of the main static magnetic field. Measurements obtained for the suspensions of BIC1 through BIC3 and COMP1 using MRI susceptibility (see FIG. 8) showed that the control microspheres had a fractional paramagnetic volume susceptibility (corrected for the effects of the suspending medium) of 0.0264 ppm (SI units) relative to the control microspheres themselves, whereas the BIC1, BIC2 and BIC3 microspheres had a fractional diamagnetic volume susceptibility (corrected for the effects of the suspending medium) of −0.0074 ppm, −0.0119 ppm and −0.019 ppm, respectively, relative to the microspheres themselves.
[0211] Since the magnetic moment of a diamagnetic material is (by definition) opposite to the main magnetic field and the torque (calculated from the vector product of the magnetic moment and the main magnetic field T=μ×B) is zero, there is no risk of particle rotational torque in BIC1, BIC2, or BIC3 microspheres. Nevertheless, none of the microsphere formulations exhibits a risk of particle rotational torque, since the magnetic moment is near zero for all samples tested, including the control microspheres.
[0212] Magnetically Induced Displacement Force Displacement forces, which pose a risk of shocking the device into the MRI system (or into the patient's body), are calculated from the interaction of the magnetic moment of the device with the rate of change through space of the MRI system's main static magnetic field. This spatial main magnetic field gradient is typically greatest near the entrance of the MRI system (the entrance hole) and is approximately 15 Tesla / M or less for a typical 3T clinical MRI system (e.g., 14.7T / m for the GE Healthcare MR750 3T MRI, as specified in the safety section of the operating manual).
[0213] Specifically, the displacement force is calculated from the dot product of the magnetic moment (μ) and the static magnetic field gradient (gradient (B)) by the formula [F = μ·gradient (B)]. Paramagnetic materials, such as BIC2 microparticles, develop a magnetic moment only as a result of exposure to a strong magnetic field and align in the same direction as the applied field. In contrast, diamagnetic materials, such as BIC1, BIC2, and BIC3 microparticles, develop a magnetic moment only as a result of exposure to a strong magnetic field and align in the opposite direction to the applied field. Nevertheless, the induced forces for all microparticle formulations are on the order of ppm (μ = V*ΔX, where V is the radio-opaque MS volume), small compared to the forces of Brownian motion (dispersion of particles), and therefore do not present a risk for magnetically induced displacement forces.
[0214] Radiofrequency (RF) heating of tissue As discussed by Parmar et al. in “Size-Dependent Heating Efficiency of Iron Oxide Single-Domain Nanoparticles” Procedia Engineering (2015) Volume 102, pages 527-533, RF heating of magnetized particles occurs primarily through a magnetic heating mechanism, rather than an inductive mechanism (electrical conduction). Magnetic heating from an RF magnetic field can occur either through the Neel mechanism (the internal magnetic moment of the particle rotates with the applied RF magnetic field without rotating the particle) or the Brownian mechanism (the particle physically rotates under the influence of the RF rotating magnetic field which produces resistive heating). These mechanisms are relevant for iron oxide nanoparticles for applications such as magnetically mediated hyperthermia (MMH) and therapeutic applications (targeted cancer ablation). These particles can create hypothermic conditions (local temperature rise of 2°C to 4°C) only under conditions involving RF magnetic fields on the order of 10 kA / M.
[0215] In contrast, MRI systems generate a peak RF field of about 0.1 kA / M (1 Gauss), or two orders of magnitude weaker than MMH applications. In addition, superparamagnetic iron oxide (SPIO) particles have a magnetic moment about five orders of magnitude greater than the microsphere formulations (0.0264 ppm (COMP1) vs. 0.0074 ppm (BIC1), -0.0119 ppm (BIC2), and -0.019 ppm (BIC3)). The BIC1, BIC2, and BIC3 microspheres of the present disclosure are weakly paramagnetic / diamagnetic materials, and therefore have negligible magnetic heating capabilities compared to SPIO agents.
[0216] In addition, SPIO nanoparticles are FDA approved contrast agents (e.g., Ferridex) and do not pose problems with RF heating, even though they are metal oxide particles like the BIC1 to BIC3 formulations and have a much larger magnetic moment. The RF heating capability of BIC microparticles is several orders of magnitude weaker than these SPIO agents, and due to their weak magnetic moment, BIC microparticles should not pose a risk of tissue heating in an MRI environment.
[0217] In vitro cytotoxicity In vitro cytotoxicity screening demonstrated that cell viabilities exposed to extracts of experimental negative and positive control materials were >70% and <70%, respectively, validating the analytical method. Formulations meeting the requirements of the study exhibited cell viability greater than or equal to 70% of untreated controls. Table 8 shows the cell viability results obtained for each microsphere formulation before treatment at various dilution series. [Table 8]
[0218] COMP1 item showed no cytotoxicity and cell viability of 98-94%. In contrast, most of the TRCR microparticle formulations were considered to have no cytotoxic potential, except for TRCR13 undiluted test (48% cell viability). All other TRCR formulations showed cell viability of 75%-112% (undiluted, undiluted). Regarding BIC microsphere formulations, two out of three, namely BIC2 (100%-105%) and BIC3 (72%-103%), showed no cytotoxicity. Cell viability of BIC1 was 22% (undiluted, undiluted) and 44% (50% diluted), indicating dose-dependent cytotoxicity.
[0219] In vitro genotoxicity The background flora of DMSO and saline test extracts for both the COMP1 article and the untreated BIC2 microspheres appeared normal. In no case did the mean number of revertants for test strains TA98, TA100, and WP2uvrA increase by more than two-fold in the presence of DMSO and saline test extracts, and in no case did the mean number of revertants for test strains TA1535 and TA1537 increase by more than three-fold. The negative control results for each test strain showed a characteristic number of spontaneous revertants according to historical data collected by the testing company. The mean value for each positive control showed at least a three-fold increase over the mean value of the negative control for each of the five test strains. The results are summarized in Table 9, and both the DMSO and saline extracts of the control article and the BIC microparticle formulations were considered to be non-mutagenic to the Salmonella typhimurium test strains TA98, TA100, TA1535, and TA1537, and the E. coli test strain WP2uvrA. [Table 9]
[0220] In vitro cytotoxicity and hemolysis of treated microspheres Table 10 shows repeated cytotoxicity and / or hemolysis evaluations of BIC2 microspheres treated for 24-72 hours. In vitro cytotoxicity confirmed the validity of the test method with media control cells exhibiting normal growth characteristics after the cell exposure step when observed under magnification. The positive control extract (undiluted) reduced the viability of the media control below 70%, whereas the negative control extract did not reduce the viability of the media control below 70%. In summary, BIC2 microspheres treated for 24 and 27 hours showed no cytotoxicity (i.e., cell viability (CV) >70%) in a series of dilutions tested from 12.5% to 50% vs. neat (undiluted), with cell viabilities ranging from 82% to 84% and 88% to 92%, respectively. We subsequently confirmed that the extended extraction step to 72 ± 2 h prior to MTT analysis did not adversely affect in vitro cytotoxicity compared to untreated (0 h) BIC2 microspheres, which showed cell viability ranging from 100% to 105% after 24 ± 2 h of extraction.
[0221] For in vitro hemolysis (direct and indirect contact hemolysis), the difference in hemolysis index between treated BIC2 microspheres and the experimental negative control was less than 2% in all test conditions, confirming the validity of the test method. According to ASTM F756:2017, a hemolysis rate of 0-2 represents a non-hemolytic reaction, and 2-5 represents a mild hemolytic reaction, whereas a reaction >5 indicates a hemolytic material reaction. According to this hemolysis grading system (Table 10): Processed BIC2 microparticles prepared using a mass / volume extraction ratio of 0.2 g / mL were considered non-hemolytic, with hemolytic activity ranging from 1.29% to 0.29% (direct contact method) for 24 to 72 hours of treatment, respectively, and 0.00% to 0.00% (indirect contact method) for 24 to 360 hours of treatment, respectively. Processed BIC2 microparticles prepared using a surface area (SA) / volume extraction ratio of 0.2 g / mL were also considered non-hemolytic, with SA ranging from 0.00% to 0.00% when processed for 24 to 72 hours, respectively (direct contact method). [Table 10]
[0222] The data presented in Table 10 confirm that BIC2 microspheres subjected to accelerated processing parameters (80°C for 24 hours) had no adverse effects on cytotoxicity (82%-92% after processing vs. 100%-106% after spheronization) or hemolysis, despite the apparent lack of surface cleanliness observed by SEM in Figure 2. Nevertheless, a 72 hour treatment time frame was observed to significantly reduce the hemolysis rate by direct contact method to 0.29.
[0223] In the preceding description, for purposes of explanation, numerous details are set forth in order to provide a thorough understanding of the embodiments. However, it will be apparent to one skilled in the art that these specific details are not required. Thus, what has been described is merely illustrative of applications of the described embodiments, and many modifications and variations are possible in light of the above teachings.
[0224] Because the above description provides examples, it will be understood that modifications and variations may be implemented to the particular examples by those skilled in the art. Accordingly, the claims should not be limited to the specific examples described herein, but should be construed in a manner consistent with the specification as a whole.
Claims
1. A glass material, the glass comprising: About 0.55 to about 0.85 mole fraction of SiO 2 and, About 0.01 to about 0.23 mole fraction of Na 2 O.K. 2 O or Na 2 O and K 2 and a combination of O. about 0.05 to about 0.28 mole fraction of Y 2 O 3 , BaO, or Y 2 O 3 and BaO; About 0.05 to about 0.12 mole fraction of Ta 2 O 5 and, Maximum 0.20 mole fraction B 2 O 3 and The Y 2 O 3 , the BaO, and the Ta 2 O 5 is from about 0.10 to about 0.31 mole fraction; The glass material comprises less than 0.01 mole fraction of Li2O.
2. The glass material of claim 1, wherein the glass comprises about 0.05 to about 0.10 mole fraction of Ta 2 O 5 .
3. The glass may have from about 0.03 to about 0.23 mole fraction, for example from about 0.05 to about 0.23 mole fraction of Na 2 O.K. 2 O or Na 2 O and K 2 3. The glass material of claim 1 , further comprising a blend of O.
4. The glass may have from about 0.55 to about 0.82 mole fraction, for example from about 0.55 to about 0.80 mole fraction of SiO 2 The glass material according to any one of claims 1 to 3, comprising:
5. The glass is About 0.55 to about 0.80 mole fraction of SiO 2 and, About 0.05 to 0.22 mole fraction of Na 2 O.K. 2 O or Na 2 O and K 2 2. The glass material of claim 1 , comprising a blend of:
6. The Y 2 O 3 , the BaO, and the Ta 2 O 5 The glass material according to any one of claims 1 to 5, wherein the sum of is about 0.10 to about 0.25 mole fraction, for example, about 0.10 to about 0.15 mole fraction.
7. The glass may have from about 0.05 to about 0.12, e.g., from about 0.05 to about 0.08 mole fraction of Y. 2 O 3 , BaO, or Y 2 O 3 The glass material according to any one of claims 1 to 6, comprising a blend of:
8. B 2 O 3 and the SiO 2 is from about 0.60 to about 0.85, for example, from about 0.60 to about 0.80 mole fraction.
9. The glass contains BaO and Na 2 O, and the BaO and the Na 2 The glass material according to any one of claims 1 to 8, wherein the sum of O is from about 0.10 to about 0.33 mole fraction, e.g., from about 0.15 to about 0.33 mole fraction, from about 0.10 to about 0.25 mole fraction, or from about 0.15 to about 0.25 mole fraction.
10. The SiO 2 and the Na 2 10. The glass material of claim 1, wherein the total of O is from about 0.65 to about 0.90 mole fraction.
11. The SiO 2 and the Na 2 the sum of O is from about 0.69 to about 0.90 mole fraction; The glass has about 0.05 to about 0.09 mole fraction of Ta. 2 O 5 and The Y 2 O 3 , the BaO, and the Ta 2 O 5 is about 0.10 to about 0.17 mole fraction.
12. About 0.55 to about 0.82 mole fraction, for example, about 0.55 to 0.75 mole fraction of SiO 2 ; About 0.03 to about 0.23 mole fraction, for example, about 0.05 to about 0.22 mole fraction of Na 2 O; about 0.05 to about 0.12 mole fraction, for example, about 0.05 to about 0.08 mole fraction of Y 2 O 3 , BaO, or Y 2 O 3 and BaO; and About 0.05 to about 0.12 mole fraction, for example, about 0.05 to about 0.09 mole fraction of Ta 2 O 5 ; Optionally, up to 0.1 mole fraction of B 2 O 3 Including, The glass material of claim 1.
13. About 0.65 to about 0.82 mole fraction, for example, about 0.73 to about 0.80 mole fraction of SiO 2 ; About 0.03 to about 0.23 mole fraction, for example, about 0.03 to about 0.11 mole fraction of Na 2 O; BaO from about 0.06 to about 0.12 mole fraction, e.g., from about 0.07 to about 0.10 mole fraction; Ta from about 0.06 to about 0.12 mole fraction, for example, from about 0.07 to about 0.10 mole fraction 2 O 5 and About 0.001 to about 0.015 mole fraction, for example, about 0.001 to about 0.006 mole fraction of B 2 O 3 Including, 13. The glass material of claim 12.
14. A composition comprising: about 0.69 mole fraction SiO 2 ; About 0.16 mole fraction Na2O; About 0.07 mole fraction of BaO; about 0.07 mole fraction of Ta2O5; and about 0.012 mole fraction of B2O3; 13. The glass material of claim 12.
15. Rb 2 O.V. 2 O 5 , ZnO, Fe 2 The glass material according to any one of claims 1 to 14, which is substantially free of one or more of O and fluoride.
16. The glass, SiO2; Na2O, K2O, or a combination of Na2O and K2O; Y2O3, BaO, or a blend of Y2O3 and BaO; Ta2O5; and It consists of B 2 O 3 , The glass material according to any one of claims 1 to 15.
17. The glass material according to claim 1, wherein the glass material is a particulate glass material configured to have a shape and particle diameter suitable for vascular embolization.
18. The glass material according to any one of claims 1 to 16, wherein the glass material is an irregular particulate glass material, for example having an average diameter of about 15 μm to about 1200 μm.
19. 1. A particulate glass material, comprising:
16. A substantially spherical shape obtained by spheronization of the irregular particulate glass material according to claim 15; Preferably, the average diameter is from about 15 μm to about 1200 μm, e.g., from about 15 μm to about 35 μm; from about 40 μm to about 500 μm; from about 40 μm to about 300 μm; from about 300 μm to about 500 μm; from about 500 μm to about 700 μm; or from about 700 μm to about 1200 μm; Optionally, a particulate glass material for use in radiological imaging, computed tomography (CT) imaging, cone beam CT imaging, or fluoroscopic imaging.
20. A particulate glass material having a substantially spherical shape, comprising: The glass material is a glass material according to any one of claims 1 to 16, The particulate glass material has an average diameter of about 15 μm to about 1200 μm.
21. A mixture of particulate glass material according to claim 19 or 20 and radioactive glass particulates, the particulate glass material and the radioactive glass particles are substantially the same size, e.g., the difference in average size of the particulate glass material and the radioactive glass particles is within 40%, or within 10%, of the average of the two average sizes; Preferably, said particulate glass material and said radioactive glass particles have substantially the same density, e.g. a mixture in which the difference in average size of said particulate glass material and said radioactive glass particles is within 30%, preferably within 15%, of the average of the two average sizes.
22. The glass material is 0.65-0.82 mole fraction of SiO 2 ; 0.03-0.23 mole fraction of Na 2 O; 0.06-0.12 mole fraction of BaO; 0.06-0.12 mole fraction of Ta 2 O 5 ; 0.001 to 0.015 mole fraction of B 2 O 3 ; and Contains less than 0.01 mole fraction of Li2O; 22. The mixture of claim 21.
23. The glass material comprises: about 0.69 mole fraction SiO2; About 0.16 mole fraction Na2O; About 0.07 mole fraction of BaO; about 0.07 mole fraction of Ta2O5; and about 0.012 mole fraction of B2O3; 22. The mixture of claim 21.
24. The mixture of claim 21, wherein the radioactive glass particulate is an yttrium oxide aluminosilicate glass.
25. The mixture of claim 24, wherein the yttrium oxide aluminosilicate glass is a glass comprising, by weight, 40% SiO 2 , 20% Al 2 O 3 , and 40% Y 2 O 3 .
Citation Information
Patent Citations
Preform glass composition for gradient index lens
JP2001139341A
radioembolic particles
JP2017537152A